Battery monomer, battery device and electric device
By using stacked positive electrode current collector and positive electrode film layers in the positive electrode sheet of the battery, and using materials such as carbon nanotubes and lithium manganese iron phosphate in different regions, the problem of high DC resistance of the battery is solved, and the conductivity and cyclic stability of the battery are improved.
Patent Information
- Application Number
- CN202411666563.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-11-20
AI Technical Summary
The existing batteries have high DC resistance, which affects the battery's performance and cycle stability.
The conductivity of the electrode sheet is improved by stacking the positive electrode current collector and the positive electrode film layer, and using different types of materials such as carbon nanotubes and lithium manganese iron phosphate in different regions of the positive electrode film layer.
The DC resistance of the battery is reduced, and the conductivity and cycling stability of the battery are improved.
Smart Images

Figure CN119674355A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of batteries, and in particular to a battery cell, a battery device and an electrical device. Background Art
[0002] With the development of new energy technology, batteries are used more and more widely, such as in mobile phones, laptops, battery cars, electric cars, energy storage devices, electric airplanes, electric ships, electric toy cars, electric toy ships, electric toy airplanes and electric tools, etc. This places higher and higher requirements on battery performance. Summary of the invention
[0003] In view of the above problems, the present application provides a battery cell, a battery device and an electrical device, which reduce the DC resistance of the battery by improving the conductivity of the electrode sheet.
[0004] In a first aspect, the present application provides a battery cell, the battery cell comprising a positive electrode sheet and a negative electrode sheet stacked in layers;
[0005] The positive electrode sheet comprises a positive electrode current collector and a positive electrode film layer located on at least one side surface of the positive electrode current collector;
[0006] The positive electrode film layer has a first surface away from the positive electrode current collector and a second surface arranged opposite to the first surface;
[0007] The distance between the first surface and the second surface is H;
[0008] Along the stacking direction of the electrode sheets, the area extending from the second surface of the positive electrode film layer to the position of 0.1×H is recorded as the first area of the positive electrode film layer;
[0009] Along the stacking direction of the electrode sheets, the area extending from the first surface of the positive electrode film layer to the position of 0.1×H is recorded as the second area of the positive electrode film layer;
[0010] The first region includes a first positive electrode active material and a first carbon nanotube, and the second region includes a second positive electrode active material and a second carbon nanotube;
[0011] The first positive electrode active material includes any one or more of lithium iron manganese phosphate and lithium manganese phosphate;
[0012] The second positive electrode active material includes any one or more of lithium manganese iron phosphate and lithium iron phosphate.
[0013] The battery cell provided in the present application is beneficial to improving the conductivity of the entire positive electrode plate to reduce the DC resistance of the battery. At the same time, it can also reduce the dissolution of manganese in the positive electrode film layer to improve the cycle or storage stability of the battery.
[0014] In some embodiments, the mass percentage content of the first carbon nanotubes in the first region is W1; the mass percentage content of the second carbon nanotubes in the second region is W2; and W1≥W2.
[0015] The mass percentage content of the first carbon nanotube in the first region in the present application is W1; the mass percentage content of the second carbon nanotube in the second region is W2; W1≥W2. The mass percentage content here is obtained by converting the amount of carbon nanotubes added when preparing the positive electrode film layer. Since the properties of carbon nanotubes in the positive electrode film layer are relatively stable, the loss amount is ignored in this application. In fact, when taking a high-magnification scanning electron microscope image of the positive electrode film layer, the content relationship between the two can be estimated based on the dispersion amount of carbon nanotubes.
[0016] In some embodiments, the mass percentage content of the first carbon nanotube in the first region is W1 which satisfies: 0<W1≤1%;
[0017] The mass percentage content of the second carbon nanotubes in the second region is W2 which satisfies: 0<W2≤1%.
[0018] In the present application, the content of carbon nanotubes in the positive electrode film layer affects its conductivity. Generally speaking, the higher the content, the stronger the conductivity. However, carbon nanotubes with a high content are not easy to disperse during preparation, which will affect their conductivity. In the present application, on the premise of being as dispersed as possible, the above-mentioned W1 or W2 is independently selected from any value below 1%, except the value zero, to further enhance the conductivity of the positive electrode active material.
[0019] In some embodiments, the first carbon nanotube or the second carbon nanotube each independently comprises any one or more of single-walled carbon nanotubes or multi-walled carbon nanotubes.
[0020] The single-walled carbon nanotube in this application refers to a single cylindrical layer of carbon atoms, and the multi-walled carbon nanotube in this application refers to two or more layers of carbon atoms connected by intermolecular forces, or a single layer of carbon atoms wrapped several times around a cylindrical hollow core. This application uses a high-power electron microscope to determine the type of carbon nanotubes in the electrode, and uses a high-power electron microscope to calculate the average diameter of the carbon nanotubes to separate single-walled carbon nanotubes and multi-walled carbon nanotubes.
[0021] In the present application, both single-walled carbon nanotubes and multi-walled carbon nanotubes, because they both contain a one-dimensional tubular structure, can exhibit good conductivity after being well dispersed in the positive electrode film layer.
[0022] In some embodiments, the first carbon nanotubes include single-walled carbon nanotubes; the single-walled carbon nanotubes satisfy any one or more of the following properties:
[0023] Average tube length>50μm; aspect ratio is 10-20; specific surface area is 800m 2 / g~1600m 2 / g.
[0024] In some embodiments, the second carbon nanotubes include multi-walled carbon nanotubes; the multi-walled carbon nanotubes satisfy any one or more of the following properties:
[0025] The average tube length is 5μm to 50μm; the aspect ratio is 1.2 to 2.0; the specific surface area is 170m 2 / g~220m 2 / g.
[0026] The carbon nanotubes of the present application have a one-dimensional tubular structure, and the diameter of the carbon nanotubes refers to the outer diameter of the carbon nanotubes. Generally speaking, the diameter of single-walled carbon nanotubes is smaller than that of multi-walled carbon nanotubes.
[0027] The tube length of the carbon nanotube in the present application refers to the value measured along both ends of the one-dimensional tubular structure.
[0028] The aspect ratio of the carbon nanotubes in the present application refers to the ratio between the tube length and the tube diameter of the carbon nanotubes.
[0029] The method for determining the specific surface area of the carbon nanotubes in the present application includes conventional known methods in the art, such as using a test instrument ASAP2460-physical adsorption analyzer, according to GB / T19587-2017: placing the carbon nanotube sample after drying and degassing in liquid nitrogen, adjusting different test pressures, measuring the adsorption amount of nitrogen respectively, and drawing adsorption and desorption isotherms, and calculating the specific surface area BET of the carbon nanotubes based on the adsorption and desorption isotherms.
[0030] The present application can use a high-power electron microscope to determine the type of carbon nanotubes in the electrode piece, and use a high-power electron microscope to calculate the average tube length and aspect ratio in the carbon nanotube slurry. In fact, when the carbon nanotubes of the present application are well dispersed in the positive electrode film layer, the changes in the values of the tube length, aspect ratio and specific area BET of the carbon nanotubes are not large and can be ignored.
[0031] The present application selects single-walled carbon nanotubes and multi-walled carbon nanotubes having the above-mentioned numerical ranges, which are beneficial for use with positive electrode active materials to further improve the conductivity of the positive electrode sheet.
[0032] In some embodiments, the first positive electrode active material includes any one or more of lithium manganese iron phosphate and lithium manganese phosphate;
[0033] The second positive electrode active material includes lithium iron phosphate.
[0034] As mentioned above, the conductivity of lithium iron phosphate is better than that of lithium iron manganese phosphate and lithium manganese phosphate, and since lithium iron phosphate does not contain manganese, there is basically no manganese dissolution. The present application selects the second positive electrode active material in the second region away from the positive electrode current collector to have a conductivity equal to or stronger than the conductivity of the first positive electrode active material in the first region close to the positive electrode current collector, which is beneficial to improving the poor conductivity in the positive electrode film layer region away from the positive electrode current collector. At the same time, the first positive electrode active material in the first region is used in combination with an equal or greater amount of carbon nanotubes than the second positive electrode active material in the second region, which further improves the uniformity of the conductivity of the entire positive electrode sheet.
[0035] At the same time, due to the Jahn-Taylor effect of manganese atoms in lithium manganese iron phosphate, the material structure is unstable, resulting in manganese dissolution and thus affecting the cycle stability of the battery. To solve this problem, the design method provided in the present application makes the second positive electrode active material in the second region away from the positive electrode current collector include lithium iron phosphate. Since lithium iron phosphate does not contain manganese, there is basically no manganese dissolution phenomenon, and the first positive electrode active material in the first region close to the positive electrode current collector includes any one or more of lithium manganese iron phosphate and lithium manganese phosphate; since the first region close to the positive electrode current collector is less likely to be fully infiltrated with the electrolyte than the second region far from the positive electrode current collector, it is beneficial to reduce the probability of manganese dissolution in the first positive electrode active material in the first region close to the positive electrode current collector.
[0036] In some embodiments, the chemical formula of the lithium manganese iron phosphate is:
[0037] Li a N b Fe x Mn y M 1-x-y P 1-m Q m O 4-n R n ;
[0038] Wherein, N represents a lithium doping element, and the lithium doping element includes any one or more of Zn, Al, Na, K, Mg, Nb, Mo and W;
[0039] M represents a doping element at the manganese position and the iron position, and the doping element at the manganese position and the iron position includes any one or more of Al, Cu, Mg, Zn, Ni, Ti, V, Zr, Co, Ga, Sn, Sb, and Nb;
[0040] Q represents a doping element at the phosphorus site, and the doping element at the phosphorus site includes any one or more of B, S, Si and N;
[0041] R represents a doping element of an oxygen site, and the doping element of the oxygen site includes any one or more of S, F, Cl and Br;
[0042] a is 0.9 to 1.1;
[0043] b is 0 to 0.1;
[0044] x is 0.001 to 0.999;
[0045] y is 0.001 to 0.999;
[0046] 1-xy is 0 to 0.1;
[0047] m is 0 to 0.1;
[0048] n is 0 to 0.1; the above-mentioned lithium manganese iron phosphate material is electrically neutral.
[0049] In some embodiments, the doping elements at the manganese and iron positions include any one or more of Al, Mg, and Ni;
[0050] 1-xy is 0.01 to 0.1.
[0051] In some embodiments, the first positive electrode active material includes a first lithium manganese iron phosphate, and the molar percentage content of manganese element in the first lithium manganese iron phosphate is Y1;
[0052] The second positive electrode active material includes a second lithium manganese iron phosphate, and the molar percentage content of manganese element in the second lithium manganese iron phosphate is Y2;
[0053] Y1 ≥ Y2;
[0054] The above Y1 and Y2 are each independently selected from y×100%.
[0055] In some embodiments, the positive electrode film layer comprises a first sub-positive electrode film layer and a second sub-positive electrode film layer stacked in sequence;
[0056] The first sub-positive electrode film layer is located on at least one side surface of the positive electrode current collector;
[0057] The second sub-positive electrode film layer is located on a side of the first sub-positive electrode film layer away from the positive electrode current collector;
[0058] The first positive electrode film layer comprises a first lithium manganese iron phosphate and a first carbon nanotube, wherein the molar percentage content of manganese element in the first lithium manganese iron phosphate is Y1, 80%<Y1<100%; the mass percentage content of the first carbon nanotube in the first positive electrode film layer is W1, 0.5%<W1≤1%;
[0059] The second sub-positive electrode film layer comprises a second lithium manganese iron phosphate and a second carbon nanotube. The molar percentage content of manganese element in the second lithium manganese iron phosphate is Y2, 0<Y2≤20%; the mass percentage content of the second carbon nanotube in the second sub-positive electrode film layer is W2, 0<W2≤0.5%.
[0060] According to the above description, the conductivity of the second positive electrode active material in the second region away from the positive electrode current collector is stronger than the conductivity of the first positive electrode active material in the first region close to the positive electrode current collector, which is beneficial to improving the phenomenon of poor conductivity in the positive electrode film layer region away from the positive electrode current collector. On this basis, the first positive electrode active material in the first region is used in combination with a larger amount of carbon nanotubes than the second positive electrode active material in the second region, which is beneficial to further improve the conductivity of the entire positive electrode film layer and evenly distribute it in various regions, so as to improve the conductivity of the electrode sheet and reduce the DC resistance of the battery.
[0061] In some embodiments, the positive electrode film layer comprises a first sub-positive electrode film layer, a third sub-positive electrode film layer and a second sub-positive electrode film layer stacked in sequence;
[0062] The first sub-positive electrode film layer is located on at least one side surface of the positive electrode current collector;
[0063] The second sub-positive electrode film layer is located on a side of the first sub-positive electrode film layer away from the positive electrode current collector;
[0064] The third sub-positive electrode film layer is located between the first sub-positive electrode film layer and the second sub-positive electrode film layer;
[0065] The first positive electrode film layer comprises a first lithium manganese iron phosphate and a first carbon nanotube, the molar percentage content of manganese element in the first lithium manganese iron phosphate is Y1, 60%<Y1<100%; the mass percentage content of the first carbon nanotube in the first positive electrode film layer is W1, 0.8%<W1≤1%;
[0066] The third positive electrode film layer comprises a third lithium manganese iron phosphate and a third carbon nanotube, wherein the molar percentage content of manganese element in the third lithium manganese iron phosphate is Y3, 20%<Y3≤60%; the mass percentage content of the third carbon nanotube in the third positive electrode film layer is W3, 0.4<W3≤0.8%;
[0067] The second sub-positive electrode film layer comprises a second lithium manganese iron phosphate and a second carbon nanotube. The molar percentage content of manganese element in the second lithium manganese iron phosphate is Y2, 0<Y2≤20%; the mass percentage content of the second carbon nanotube in the second sub-positive electrode film layer is W2, 0<W2≤0.4%.
[0068] In some embodiments, the positive electrode film layer further comprises any one or more of carbon black and graphene;
[0069] The specific surface area of the above carbon black is ≥100m 2 / g;
[0070] and / or;
[0071] The number of layers of the graphene is 1 to 10, and the average sheet diameter of each layer is 2 μm to 8 μm;
[0072] and / or;
[0073] The mass percentage content of the carbon black and / or graphene in the positive electrode film layer is 0 to 2.5%.
[0074] In the present application, the conductive agent in the positive electrode film layer may only include carbon nanotubes with a one-dimensional tubular structure, and may also include one or two of carbon black and graphene, wherein graphene has a flake structure and carbon black has a dot structure. In some embodiments of the present application, a conductive agent is selected for use in combination, such as one-dimensional tubular structure + flake structure graphene + dot-shaped carbon black, which is beneficial to improve the conductivity of the positive electrode plate by constructing a conductive network.
[0075] In some embodiments, the positive electrode film layer further comprises a dispersant, and the dispersant comprises any one or more of hydrogenated nitrile rubber and its modified compounds, polyvinylidene fluoride and its modified compounds;
[0076] The weight average molecular weight of the hydrogenated nitrile rubber and its modified compound is 50,000 to 150,000;
[0077] and / or;
[0078] The hydrogenated nitrile rubber and its modified compound contain structural units derived from acrylonitrile monomers, and the mass percentage content of the structural units derived from acrylonitrile monomers in the hydrogenated nitrile rubber and its modified compound is 20% to 40%;
[0079] and / or;
[0080] The degree of hydrogenation of the above hydrogenated nitrile rubber and its modified compounds is ≥99%;
[0081] and / or;
[0082] The weight average molecular weight of the polyvinylidene fluoride and its modified compounds is 2 million to 4 million;
[0083] and / or;
[0084] The crystallinity of the polyvinylidene fluoride and its modified compounds is 40% to 60%.
[0085] The present application uses carbon nanotubes as a conductive agent in the positive electrode film layer, but the one-dimensional tubular carbon nanotubes are not easily dispersed well and agglomerate, thereby affecting the conductivity. In order to disperse the carbon nanotubes well, the present application selects to add a certain type and a certain amount of dispersant.
[0086] In some embodiments, the film resistance of the positive electrode sheet is less than or equal to 1Ω.
[0087] In some embodiments, the film resistance of the positive electrode sheet is 0.1Ω to 1Ω.
[0088] The diaphragm resistance in the present application can be used to measure the conductivity of the electrode. The test of the diaphragm resistance of the positive electrode of the present application can be carried out by methods known in the art, such as the four-probe method. The positive electrode is cut into 3*3mm small discs along the left, middle and right sides by the Yuanneng Technology electrode resistance meter test device, and placed in the sample placement area of the resistance meter test device, and the device is turned on to measure the resistance value.
[0089] In some embodiments, the particle size of the first positive electrode active material and / or the second positive electrode active material satisfies: Dv50 is 0.5 μm to 1.5 μm.
[0090] In some embodiments, a carbon coating layer is formed on the outer side of the particles of the first positive electrode active material and / or the second positive electrode active material, and the thickness of the carbon coating layer is 0.01 μm to 1 μm.
[0091] In some embodiments, a distance H between the first surface and the second surface is 0.1 mm to 0.2 mm.
[0092] A second aspect of the present application is to provide a battery device, comprising the secondary battery described in the first aspect.
[0093] The third aspect of the present application is to provide an electrical device, comprising the battery device described in the second aspect.
[0094] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0095] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present application. Moreover, the same reference numerals are used throughout the accompanying drawings to represent the same components. In the accompanying drawings:
[0096] Figure 1 A schematic diagram of the battery structure of some embodiments of the present application;
[0097] Figure 2 This is a schematic diagram of the exploded structure of batteries in some embodiments of the present application;
[0098] Figure 3 A schematic diagram of a vehicle structure of some embodiments of the present application;
[0099] Figure 4 A schematic diagram of the structure of a battery pack according to some embodiments of the present application;
[0100] Figure 5 A schematic diagram of the structure of a battery in some embodiments of the present application;
[0101] Figure 6 A schematic diagram of the structure of a positive electrode sheet of some embodiments of the present application;
[0102] Figure 7 Another structural schematic diagram of the positive electrode sheet of some embodiments of the present application;
[0103] Figure 8 Another structural schematic diagram of the positive electrode sheet of some embodiments of the present application;
[0104] The reference numerals in the specific implementation manner are as follows:
[0105] 10000, vehicles;
[0106] 1000, battery; 2000, controller; 3000, motor;
[0107] 100. Battery cell;
[0108] 200, box body; 210, first part; 220, second part;
[0109] 10. Secondary battery;
[0110] 101, housing; 102, electrode assembly; 103, cover plate;
[0111] 1. Negative electrode;
[0112] 2. positive electrode plate; 21. positive electrode current collector; 22. positive electrode film layer;
[0113] 3. Isolation film;
[0114] 22a, first surface; 22b, second surface;
[0115] 22A, first area; 22B, second area;
[0116] 222, a first sub-positive electrode film layer;
[0117] 221, second sub-positive electrode film layer;
[0118] 223. The third sub-positive electrode film layer.
[0119] Coordinate axis x direction: the stacking direction or thickness direction of the pole piece;
[0120] Coordinate axis y direction: length direction or width direction of the pole piece. DETAILED DESCRIPTION
[0121] Hereinafter, the battery cells, battery devices and power devices of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0122] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0123] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0124] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0125] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0126] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0127] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0128] If not otherwise specified, in this application, the terms "first", "second", etc. are only used to distinguish different objects and cannot be understood as indicating or implying relative importance or implicitly indicating the quantity, specific order or primary and secondary relationship of the indicated technical features.
[0129] Unless otherwise specified, in this application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple sheets" refers to more than two sheets (including two sheets).
[0130] Unless otherwise specified, the orientations or positional relationships indicated by technical terms such as "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", and "circumferential" are based on the orientations or positional relationships shown in the accompanying drawings and are only for the convenience of describing the embodiments of the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the embodiments of the present application.
[0131] Batteries have been widely used in various products due to their advantages such as high energy density, long cycle life, safety and reliability. In recent years, as the demand for batteries as energy has increased significantly, higher requirements have been placed on battery performance such as conductivity.
[0132] Lithium iron phosphate, lithium iron manganese phosphate, and lithium manganese phosphate positive electrode materials have gradually become the main positive electrode materials for electric vehicles or energy storage batteries due to their higher safety. In particular, the charging voltage of lithium iron manganese phosphate can be increased from 3.4V of lithium iron phosphate to 4.1V. However, in terms of electron transmission capacity, the conductivity of lithium iron manganese phosphate is several orders of magnitude lower than that of lithium iron phosphate, resulting in relatively poor conductivity of lithium iron manganese phosphate materials.
[0133] In order to improve the conductivity of lithium iron manganese phosphate materials, the present application provides a battery cell, a battery device and an electrical device.
[0134] First, the present application discloses a battery cell, which includes a stacked positive electrode sheet and a negative electrode sheet; the positive electrode sheet includes a positive electrode collector and a positive electrode film layer located on at least one side of the positive electrode collector; the positive electrode film layer has a first surface away from the positive electrode collector and a second surface arranged opposite to the first surface; the distance between the first surface and the second surface is H; along the stacking direction of the electrode sheet, the area formed by extending from the second surface of the positive electrode film layer to the position of 0.1×H is recorded as the first area of the positive electrode film layer; along the stacking direction of the electrode sheet, the area formed by extending from the first surface of the positive electrode film layer to the position of 0.1×H is recorded as the second area of the positive electrode film layer; the first area includes a first positive electrode active material and a first carbon nanotube, and the second area includes a second positive electrode active material and a second carbon nanotube; the first positive electrode active material includes any one or more of lithium iron manganese phosphate and lithium manganese phosphate; the second positive electrode active material includes any one or more of lithium iron manganese phosphate and lithium iron phosphate.
[0135] The carbon nanotubes in the present application have a one-dimensional tubular structure, which can be used in conjunction with the positive electrode active material to exert good conductivity, thereby improving the conductivity of the positive electrode sheet. At the same time, the design method provided by the present application is conducive to enhancing the conductivity of the second positive electrode active material in the second region away from the positive electrode current collector, so that the conductivity difference between the second region and the first region is reduced, which is conducive to improving the phenomenon of poor conductivity in the positive electrode film layer region away from the positive electrode current collector, thereby making the conductivity of the entire positive electrode film layer evenly distributed in each region, so as to improve the conductivity of the electrode sheet and reduce the DC resistance of the battery.
[0136] In addition, due to the Jahn-Taylor effect of manganese atoms in lithium manganese iron phosphate, the material structure is unstable, resulting in manganese dissolution and thus affecting the cycle stability of the battery. To solve this problem, the design method provided in the present application also makes the second positive electrode active material in the second region away from the positive current collector include any one or more of lithium manganese iron phosphate and lithium iron phosphate, while the first positive electrode active material in the first region close to the positive current collector includes any one or more of lithium manganese iron phosphate and lithium manganese phosphate, that is, the manganese content in the second region away from the positive current collector is relatively lower. This design method is beneficial to reducing the dissolution of manganese in the positive electrode film layer to improve the cycle or storage stability of the battery.
[0137] Therefore, the battery cell provided in this application is conducive to improving the conductivity of the entire positive electrode sheet to reduce the DC resistance of the battery, and at the same time, it can also reduce the dissolution of manganese in the positive electrode film layer to improve the cycle stability of the battery. Therefore, the design method provided in this application is conducive to increasing user experience.
[0138] Electrode assembly
[0139] A battery cell generally includes an electrode assembly. The electrode assembly includes a positive electrode sheet, a negative electrode sheet, and a separator, which is arranged between the negative electrode sheet and the positive electrode sheet. During the charge and discharge process of the battery cell, active ions (such as lithium ions) are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, which can prevent the positive and negative electrodes from short-circuiting, and at the same time allow active ions to pass through.
[0140] Battery device
[0141] The battery apparatus mentioned in the embodiments of the present application may include one or more battery cell assemblies for providing voltage and capacity. The battery cell assembly may include multiple battery cells, which are connected in series, in parallel or in mixed connection through a busbar component.
[0142] In some embodiments, a battery cell assembly is generally formed by arranging a plurality of battery cells.
[0143] As an example, the battery cell assembly may be a battery module, which is formed by arranging and fixing a plurality of battery cells to form an independent module. As an example, the battery module may be formed by bundling a plurality of battery cells by a cable tie.
[0144] In some embodiments, the battery device may be a battery pack, which includes a case and one or more battery cell assemblies, wherein the battery cell assemblies are accommodated in the case.
[0145] As an example, the battery cell assembly may be a battery module, and the battery cell assembly may be accommodated in the box by fixing the battery module in the box.
[0146] As an example, the battery cell assembly may also be housed in the case by directly fixing a plurality of battery cells to the case.
[0147] As an example, the box may include a first box and a second box. The first box and the second box are buckled together to form a closed space inside the box to accommodate the battery cell assembly. The closed here means covered or closed, which can be sealed or unsealed. The first box can be a top cover or a bottom plate.
[0148] As an example, the box body may include a top cover, a frame and a bottom plate. The top cover and the bottom plate are respectively connected to the frame, so that a closed space is formed inside the box body to accommodate the battery cell assembly.
[0149] In some embodiments, the box body can be used as a part of the chassis structure of the vehicle. For example, part of the box body can become at least a part of the floor of the vehicle, or part of the box body can become at least a part of the cross beam and longitudinal beam of the vehicle.
[0150] The battery cell of the present application may include an outer package. The outer package may be used to encapsulate the electrode assembly and electrolyte composed of the above-mentioned battery cell. The outer package of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and the plastic includes but is not limited to polypropylene, polybutylene terephthalate, and polybutylene succinate, etc.
[0151] The present application has no particular limitation on the shape of the battery, which may be cylindrical, square or any other shape. For example, Figure 1 The secondary battery 10 is a square structure as an example.
[0152] According to some embodiments of the present application, Figure 2, the outer packaging may include a shell 101 and a cover plate 103. Among them, the shell 101 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 101 has an opening connected to the receiving cavity, and the cover plate 103 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation film can form an electrode assembly 102 through a winding process or a lamination process. The electrode assembly 102 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 102. The number of electrode assemblies 102 contained in the secondary battery 10 can be one or more, and those skilled in the art can select according to specific actual needs.
[0153] The electrode assembly 102 provided in the present application is applied to a secondary battery, which is beneficial to improving the performance of the secondary battery. The secondary battery can be used as a power source for an electrical device or as an energy storage unit for an electrical device. The electrical device is applied to the power field, such as mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but not limited to the above-mentioned fields.
[0154] For the convenience of explanation, some embodiments of the present application are described by taking a vehicle as an example of an electrical device.
[0155] Please refer to Figure 3 , Figure 3 A schematic diagram of the structure of a vehicle 10000 provided for some embodiments of the present application. The vehicle 10000 may be a fuel vehicle, a gas vehicle or a new energy vehicle, and the new energy vehicle may be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. A battery 1000 is provided inside the vehicle 10000, and the battery 1000 may be provided at the bottom, head or tail of the vehicle 10000. The battery 1000 may be used to power the vehicle 10000, for example, the battery 1000 may be used as an operating power source for the vehicle 10000. The vehicle 10000 may also include a controller 2000 and a motor 3000, and the controller 2000 is used to control the battery 1000 to power the motor 3000, for example, for the starting, navigation and working power requirements of the vehicle 10000 during driving.
[0156] In some embodiments of the present application, the battery 1000 can not only serve as the operating power source of the vehicle 10000, but also serve as the driving power source of the vehicle 10000, replacing or partially replacing fuel or natural gas to provide driving power for the vehicle 10000.
[0157] Please refer to Figure 4 , Figure 4An exploded view of a battery 1000 provided in some embodiments of the present application. The battery 1000 includes a housing 200 and a battery cell 100. Conventional battery cells include primary batteries or secondary batteries. The present application specifically protects secondary batteries 10. The battery cell 100 is accommodated in the housing 200. The housing 200 is used to provide a storage space for the battery cell 100. The housing 200 can adopt a variety of structures.
[0158] In some embodiments, the box body 200 may include a first part 210 and a second part 220, the first part 210 and the second part 220 cover each other, and the first part 210 and the second part 220 jointly define a storage space for accommodating the secondary battery 100. The second part 220 may be a hollow structure with one end open, and the first part 210 may be a plate-like structure, and the first part 210 covers the open side of the second part 220, so that the first part 210 and the second part 220 jointly define a storage space; the first part 210 and the second part 220 may also be hollow structures with one side open, and the open side of the first part 210 covers the open side of the second part 220. Of course, the box body 200 formed by the first part 210 and the second part 220 may be in various shapes, such as a cylinder, a cuboid, etc.
[0159] In the battery 1000, there may be multiple battery cells 100, and the multiple battery cells 100 may be connected in series, in parallel, or in a mixed connection. A mixed connection means that the multiple battery cells 100 are both connected in series and in parallel. The multiple battery cells 100 may be directly connected in series, in parallel, or in a mixed connection, and then the whole formed by the multiple battery cells 100 is accommodated in the box 200; of course, the battery 1000 may also be a battery 1000 module formed by connecting multiple battery cells 100 in series, in parallel, or in a mixed connection, and then the multiple battery 1000 modules are connected in series, in parallel, or in a mixed connection to form a whole, and accommodated in the box 200. The battery 1000 may also include other structures, for example, the battery 1000 may also include a busbar component for realizing electrical connection between the multiple battery cells 100.
[0160] Battery Cell
[0161] In some embodiments, the present application discloses a battery cell, which includes a stacked positive electrode sheet and a negative electrode sheet; the positive electrode sheet includes a positive electrode collector and a positive electrode film layer located on at least one side of the positive electrode collector; the positive electrode film layer has a first surface away from the positive electrode collector and a second surface arranged opposite to the first surface; the distance between the first surface and the second surface is H; along the stacking direction of the electrode sheet, the area formed by extending from the second surface of the positive electrode film layer to the position of 0.1×H is recorded as the first area of the positive electrode film layer; along the stacking direction of the electrode sheet, the area formed by extending from the first surface of the positive electrode film layer to the position of 0.1×H is recorded as the second area of the positive electrode film layer; the first area includes a first positive electrode active material and a first carbon nanotube, and the second area includes a second positive electrode active material and a second carbon nanotube; the first positive electrode active material includes any one or more of lithium iron manganese phosphate and lithium manganese phosphate; the second positive electrode active material includes any one or more of lithium iron manganese phosphate and lithium iron phosphate.
[0162] The positive electrode sheet, the separator and the negative electrode sheet of the present application can be wound or laminated to form a secondary battery. Figure 5 The secondary battery 10 is formed by a stacking method, and the Figure 5 It can be seen that a negative electrode sheet 1 or a positive electrode sheet 2 is placed between two adjacent separators 3, and the negative electrode sheets 1 and the positive electrode sheets 2 are alternately arranged in sequence along the stacking direction (coordinate axis x direction). The number and size of the negative electrode sheets 1 and / or the positive electrode sheets 2 can be selected according to actual conditions, and this application will not be repeated. Figure 5 Only one lamination method is illustrated in the figure, and other lamination or winding methods are within the protection scope of this application.
[0163] like Figure 6 As shown in the figure, the positive electrode sheet 2 includes a positive electrode current collector 21 and a positive electrode film layer 22 located on at least one side of the positive electrode current collector 21, wherein: Figure 6 The positive electrode film layer 22 is schematically provided on either side of the positive electrode current collector 21. The positive electrode film layer 22 may also be provided on both sides of the positive electrode current collector 21. The positive electrode film layer 22 may be formed on the surface of the positive electrode current collector 21 by any conventional method in the art, such as coating, deposition, etc.
[0164] This application is Figure 6 The first surface 22a and the second surface 22b of the positive electrode film layer 22 are also schematically shown. The distance between the first surface 22a and the second surface 22b is H, that is, the single-side thickness of the positive electrode film layer 22 on the positive electrode current collector is H. The measurement method of the value H includes any conventional method in the field, and the present application uses a micrometer to measure it.
[0165] In order to more conveniently describe the characteristics of different regions in the positive electrode film layer, the present application selects the region extending from the second surface 22b of the positive electrode film layer 22 to the position of 0.1×H along the stacking direction of the electrode piece as the first region 22A of the positive electrode film layer 22; and the region extending from the first surface 22a of the positive electrode film layer 22 to the position of 0.1×H along the stacking direction of the electrode piece as the second region 22B of the positive electrode film layer 22. The stacking direction of the electrode piece also refers to the thickness direction of the electrode piece. Figure 6 The x-axis direction is illustrated in the figure, that is, the positive electrode film layer area close to the positive electrode current collector is defined as the first area, and the positive electrode film layer area away from the positive electrode current collector is defined as the second area. The 0.1×H position given in this application is only for illustrating the area, and its actual numerical range has no clear meaning.
[0166] The first region of the present application includes a first positive electrode active material and a first carbon nanotube, and the second region includes a second positive electrode active material and a second carbon nanotube, wherein the first positive electrode active material includes any one or more of lithium iron manganese phosphate and lithium manganese phosphate; the second positive electrode active material includes any one or more of lithium iron manganese phosphate and lithium iron phosphate.
[0167] According to the above design ideas and descriptions, the positive electrode active material of this application includes the following design methods:
[0168] (1) The first positive electrode active material includes lithium iron manganese phosphate, and the second positive electrode active material includes lithium iron manganese phosphate;
[0169] (2) the first positive electrode active material includes lithium manganese iron phosphate, and the second positive electrode active material includes lithium iron phosphate;
[0170] (3) The first positive electrode active material includes lithium manganese phosphate, and the second positive electrode active material includes lithium iron phosphate.
[0171] The present application only lists some of the design methods above. In fact, the design method in which the first region and / or the second region contains two active substances is also within the protection scope of the present application, and the present application will not list them one by one here.
[0172] The carbon nanotube of the present application is a sp 2 A one-dimensional tubular material composed mainly of hybridized carbon atoms, which has good electron mobility.
[0173] As mentioned above, the conductivity of lithium iron manganese phosphate is several orders of magnitude lower than that of lithium iron phosphate, resulting in relatively poor conductivity of lithium iron manganese phosphate materials, and the conductivity of lithium iron manganese phosphate materials with different manganese contents is also different. Generally speaking, the conductivity of lithium iron manganese phosphate materials with higher manganese content is weaker than that of lithium iron manganese phosphate materials with low manganese content. Therefore, the present application adopts the above-mentioned method to reduce the difference between the conductivity of the second positive electrode active material in the second area away from the positive current collector and the conductivity of the first positive electrode active material in the first area close to the positive current collector, which is conducive to improving the phenomenon of poor conductivity in the positive electrode film layer area away from the positive current collector, thereby making the conductivity of the entire positive electrode film layer evenly distributed in each area.
[0174] In addition, due to the Jahn-Taylor effect of manganese atoms in lithium manganese iron phosphate, the material structure is unstable, resulting in manganese dissolution, which in turn affects the cycle or storage stability of the battery. To solve this problem, the design method provided in the present application makes the second positive electrode active material in the second region away from the positive electrode current collector include any one or more of lithium manganese iron phosphate and lithium iron phosphate, while the first positive electrode active material in the first region close to the positive electrode current collector includes any one or more of lithium manganese iron phosphate and lithium manganese phosphate. This design method is beneficial to reducing the dissolution of manganese in the positive electrode film layer to improve the cycle or storage stability of the battery.
[0175] Therefore, the battery cell provided in the present application is conducive to improving the conductivity of the entire positive electrode plate to reduce the DC resistance of the battery. At the same time, it can also reduce the dissolution of manganese in the positive electrode film layer to improve the cycle or storage stability of the battery.
[0176] In some embodiments, the mass percentage content of the first carbon nanotubes in the first region is W1; the mass percentage content of the second carbon nanotubes in the second region is W2; and W1≥W2.
[0177] The mass percentage content of the first carbon nanotube in the first region in the present application is W1; the mass percentage content of the second carbon nanotube in the second region is W2; W1≥W2. The mass percentage content here is obtained by converting the amount of carbon nanotubes added when preparing the positive electrode film layer. Since the properties of carbon nanotubes in the positive electrode film layer are relatively stable, the loss amount is ignored in this application. In fact, when taking a high-magnification scanning electron microscope image of the positive electrode film layer, the content relationship between the two can be estimated based on the dispersion amount of carbon nanotubes.
[0178] The present application selects a first positive electrode active material in the first region compared to a second positive electrode active material in the second region, and uses an equal or greater amount of carbon nanotubes with a one-dimensional tubular structure, which is beneficial to further improve the conductivity of the entire positive electrode film layer and evenly distribute it in each region, thereby improving the conductivity of the electrode sheet and reducing the DC resistance of the battery.
[0179] In some embodiments, the first carbon nanotubes or the second carbon nanotubes each independently include any one or more of single-walled carbon nanotubes or multi-walled carbon nanotubes.
[0180] The single-walled carbon nanotube in this application refers to a single cylindrical layer of carbon atoms, and the multi-walled carbon nanotube in this application refers to two or more layers of carbon atoms connected by intermolecular forces, or a single layer of carbon atoms wrapped several times around a cylindrical hollow core. This application uses a high-power electron microscope to determine the type of carbon nanotubes in the electrode, and uses a high-power electron microscope to calculate the average diameter of the carbon nanotubes to distinguish single-walled carbon nanotubes and multi-walled carbon nanotubes.
[0181] In the present application, both single-walled carbon nanotubes and multi-walled carbon nanotubes, because they both contain a one-dimensional tubular structure, can exhibit good conductivity after being well dispersed in the positive electrode film layer.
[0182] In some embodiments, the mass percentage content of the first carbon nanotube in the first region is W1 which satisfies: 0<W1≤1%;
[0183] The mass percentage content of the second carbon nanotube in the second region is W2, which satisfies: 0<W2≤1%. In the present application, the content of carbon nanotubes in the positive electrode film layer affects its conductivity. Generally speaking, under the same type, the more the content, the stronger the conductivity. However, carbon nanotubes with a large content are not easy to disperse during preparation, which will affect the performance of their conductivity. In the present application, under the premise of being dispersed as much as possible, the above W1 or W2 is independently selected from any value below 1%, except for the value of zero, to further enhance the conductivity of the positive electrode active material.
[0184] The present application discloses in these embodiments that the above-mentioned W1 or W2 each independently includes any one of 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% or any one of the numerical ranges between any two of the above.
[0185] In some embodiments, the first carbon nanotubes include single-walled carbon nanotubes; the single-walled carbon nanotubes satisfy any one or more of the following properties:
[0186] Average tube length>50μm; aspect ratio is 10-20; specific surface area is 800m 2 / g~1600m 2 / g.
[0187] In some embodiments, the second carbon nanotubes include multi-walled carbon nanotubes; the multi-walled carbon nanotubes satisfy any one or more of the following properties:
[0188] The average tube length is 5μm to 50μm; the aspect ratio is 1.2 to 2.0; the specific surface area is 170m 2 / g~220m 2 / g.
[0189] The carbon nanotubes of the present application have a one-dimensional tubular structure, and the diameter of the carbon nanotubes refers to the outer diameter of the carbon nanotubes. Generally speaking, the diameter of single-walled carbon nanotubes is smaller than that of multi-walled carbon nanotubes.
[0190] The tube length of the carbon nanotube in the present application refers to the value measured along both ends of the one-dimensional tubular structure.
[0191] The aspect ratio of the carbon nanotubes in the present application refers to the ratio between the tube length and the tube diameter of the carbon nanotubes.
[0192] The specific surface area BET of carbon nanotubes in this application refers to the specific surface area determined by nitrogen adsorption based on the Brunauer-Emmett-Teller method described in the journal "Journal of the American Chemical Society", 60, 309 (1938) according to the ASTMD 3663-78 standard. The determination method of the specific surface area BET of this application includes conventional known methods in the art, such as using the test instrument ASAP2460-physical adsorption analyzer, according to GB / T19587-2017: the carbon nanotube sample after drying and degassing is placed in liquid nitrogen, adjusting different test pressures, respectively measuring the adsorption amount of nitrogen, and drawing adsorption and desorption isotherms, and calculating the specific surface area BET of carbon nanotubes according to the adsorption and desorption isotherms.
[0193] The present application can use a high-power electron microscope to determine the carbon nanotubes in the electrode piece, and use a high-power electron microscope to calculate the average tube length and aspect ratio in the carbon nanotube slurry. In fact, when the carbon nanotubes of the present application are well dispersed in the positive electrode film layer, the changes in the values of the tube length, aspect ratio and specific area BET of the carbon nanotubes are not large and can be ignored.
[0194] The present application selects single-walled carbon nanotubes and multi-walled carbon nanotubes having the above-mentioned numerical ranges, which are beneficial for use with positive electrode active materials to further improve the conductivity of the positive electrode sheet.
[0195] The present application discloses in these embodiments that the average tube length of the single-walled carbon nanotubes is greater than 50 μm and less than or equal to 100 μm. The present application specifically discloses that the average tube length of the single-walled carbon nanotubes is 51 μm, 52 μm, 53 μm, 54 μm, 55 μm, 56 μm, 57 μm, 58 μm, 59 μm, 60 μm, 61 μm, 62 μm, 63 μm, 64 μm, 65 μm, 66 μm, 67 μm, 68 μm, 69 μm, 70 μm, 71 μm, 72 μm, 73 μm, 74 μm, 75 μm, 76 μm, Any one of μm, 77μm, 78μm, 79μm, 80μm, 81μm, 82μm, 83μm, 84μm, 85μm, 86μm, 87μm, 88μm, 89μm, 90μm, 91μm, 92μm, 93μm, 94μm, 95μm, 96μm, 97μm, 98μm, 99μm, 100μm or any one of the numerical ranges between any two of the above.
[0196] In these embodiments, the present application discloses any one of aspect ratios of 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, and 20 for single-walled carbon nanotubes, or any one of the numerical ranges between any two of the above.
[0197] The present application discloses in these examples that the specific surface area of the single-walled carbon nanotubes is 800 m 2 / g, 850m 2 / g、900m 2 / g, 950m 2 / g、1000m 2 / g, 1050m 2 / g、1100m 2 / g, 1150m 2 / g、1200m 2 / g, 1250m 2 / g、1300m 2 / g, 1350m 2 / g、1400m 2 / g, 1450m 2 / g、1500m 2 / g, 1550m 2 / g、1600m 2 / g or any of the numerical ranges between any two of the above.
[0198] In these embodiments, the present application discloses that the average tube length of the multi-walled carbon nanotubes is any one of 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 15μm, 20μm, 25μm, 30μm, 35μm, 40μm, 45μm, 50μm or any one of the numerical ranges between any two of the above.
[0199] In these embodiments, the present application discloses that the aspect ratio of the multi-walled carbon nanotubes is any one of 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0 or any one of the numerical ranges between any two of the above.
[0200] The present application discloses in these examples that the specific surface area of the multi-walled carbon nanotubes is 170 m 2 / g, 180m 2 / g, 190m 2 / g, 200m 2 / g, 210m 2 / g, 220m 2 / g or any of the numerical ranges between any two of the above.
[0201] In some embodiments, the first positive electrode active material includes any one or more of lithium iron manganese phosphate and lithium manganese phosphate; the second positive electrode active material includes lithium iron phosphate.
[0202] As mentioned above, the conductivity of lithium iron phosphate is better than that of lithium iron manganese phosphate and lithium manganese phosphate, and since lithium iron phosphate does not contain manganese, there is basically no manganese dissolution. The present application selects the second positive electrode active material in the second region away from the positive electrode current collector to have a conductivity equal to or stronger than the conductivity of the first positive electrode active material in the first region close to the positive electrode current collector, which is beneficial to improving the poor conductivity in the positive electrode film layer region away from the positive electrode current collector. At the same time, the first positive electrode active material in the first region is used in combination with an equal or greater amount of carbon nanotubes than the second positive electrode active material in the second region, which further improves the uniformity of the conductivity of the entire positive electrode sheet.
[0203] At the same time, due to the Jahn-Taylor effect of manganese atoms in lithium manganese iron phosphate, the material structure is unstable, resulting in manganese dissolution and thus affecting the cycle stability of the battery. To solve this problem, the design method provided in the present application makes the second positive electrode active material in the second region away from the positive electrode current collector include lithium iron phosphate. Since lithium iron phosphate does not contain manganese, there is basically no manganese dissolution phenomenon, and the first positive electrode active material in the first region close to the positive electrode current collector includes any one or more of lithium manganese iron phosphate and lithium manganese phosphate; since the first region close to the positive electrode current collector is less likely to be fully infiltrated with the electrolyte than the second region far from the positive electrode current collector, it is beneficial to reduce the probability of manganese dissolution in the first positive electrode active material in the first region close to the positive electrode current collector.
[0204] In some embodiments, the chemical formula of the lithium manganese iron phosphate is:
[0205] Li a N b Fe x Mn y M 1-x-y P 1-m Q m O 4-n R n ;
[0206] Wherein, N represents a lithium doping element, and the lithium doping element includes any one or more of Zn, Al, Na, K, Mg, Nb, Mo and W;
[0207] M represents a doping element at the manganese position and the iron position, and the doping element at the manganese position and the iron position includes any one or more of Al, Cu, Mg, Zn, Ni, Ti, V, Zr, Co, Ga, Sn, Sb, and Nb;
[0208] Q represents a doping element at the phosphorus site, and the doping element at the phosphorus site includes any one or more of B, S, Si and N;
[0209] R represents a doping element of an oxygen site, and the doping element of the oxygen site includes any one or more of S, F, Cl and Br;
[0210] a is 0.9 to 1.1;
[0211] b is 0 to 0.1;
[0212] x is 0.001 to 0.999;
[0213] y is 0.001 to 0.999;
[0214] 1-xy is 0 to 0.1;
[0215] m is 0 to 0.1;
[0216] n is 0 to 0.1; the above-mentioned lithium manganese iron phosphate material is electrically neutral.
[0217] The doping elements at the manganese and iron positions in the present application are beneficial to improving the electronic conductivity of the material.
[0218] In the above chemical formula of the present application, b is further 0.001 to 0.1.
[0219] In the above chemical formula of the present application, m is further 0.001 to 0.1.
[0220] In the above chemical formula of the present application, n is further 0.001 to 0.1.
[0221] In these embodiments, the present application provides that a in the chemical formula is any one of 0.9, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 1, 1.05, 1.1 or any one of the numerical ranges between any two of the above.
[0222] In these embodiments, the present application provides that b in the chemical formula is any one of 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1 or any one of the numerical ranges between any two of the above.
[0223] In these embodiments, the present application provides that x in the chemical formula is any one of 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, and 0.99, or any one of the numerical ranges between any two of the above.
[0224] In these embodiments, the present application provides that y in the chemical formula is any one of 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, and 0.99, or any one of the numerical ranges between any two of the above.
[0225] In these embodiments, the present application provides that 1-xy in the chemical formula is any one of 0, 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1 or any one of the numerical ranges between any two of the above.
[0226] In these embodiments, the present application provides that m in the chemical formula is any one of 0, 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, and 0.1, or any one of the numerical ranges between any two of the above.
[0227] In these embodiments, the present application provides that n in the chemical formula is any one of 0, 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, and 0.1, or any one of the numerical ranges between any two of the above.
[0228] In some embodiments, the doping elements at the manganese and iron sites include any one or more of Al, Mg, and Ni;
[0229] 1-xy is 0.01 to 0.1.
[0230] The lithium manganese iron phosphate selected in the present application also includes any one or more of Al, Mg, and Ni as doping elements, and controlling the doping amount of the doping element is beneficial to improving the electronic conductivity of the lithium manganese iron phosphate material, and then improving the conductivity of the positive electrode plate.
[0231] In some embodiments, the first positive electrode active material includes a first lithium manganese iron phosphate, and the molar percentage content of manganese element in the first lithium manganese iron phosphate is Y1;
[0232] The second positive electrode active material includes a second lithium manganese iron phosphate, and the molar percentage content of manganese element in the second lithium manganese iron phosphate is Y2;
[0233] Y1 ≥ Y2;
[0234] The above Y1 and Y2 are each independently selected from y×100%.
[0235] In the present application, the molar percentage content of manganese in lithium iron manganese phosphate refers to the molar percentage content of manganese in transition metal elements, and the present application provides a calculation method for the numerical range corresponding to the definition: Y1 or Y2 is independently selected from y×100%.
[0236] As mentioned above, due to the presence of the Jiang-Taylor effect of manganese atoms in lithium manganese iron phosphate, the material structure is unstable, resulting in manganese dissolution and thus affecting the cycle stability of the battery, and this problem becomes more serious as the molar percentage content of manganese in lithium manganese iron phosphate increases. The present application selects a molar percentage content of manganese in the first lithium manganese iron phosphate in the first region close to the positive electrode current collector that is greater than or equal to the molar percentage content of manganese in the second lithium manganese iron phosphate in the second region away from the positive electrode current collector. When the molar contents of the two are the same, the use of carbon nanotubes with a one-dimensional tubular structure is beneficial to improving the conductivity of the positive electrode sheet. When the two have a difference, it is obvious that the conductivity of the second positive active material in the second region away from the positive electrode current collector is stronger than the conductivity of the first positive active material in the first region close to the positive electrode current collector, which is beneficial to improve the poor conductivity in the positive electrode film region away from the positive electrode current collector. At the same time, the first positive active material in the first region is compared with the second positive active material in the second region. The use of an equal amount or more of carbon nanotubes further improves the conductivity of the entire positive electrode sheet. In addition, the second lithium manganese iron phosphate in the second area away from the positive electrode current collector is less likely to have manganese dissolution than the first lithium manganese iron phosphate in the first area close to the positive electrode current collector, and the first lithium manganese iron phosphate in the first area close to the positive electrode current collector is less likely to be fully infiltrated with the electrolyte, so both are beneficial to reducing the probability of manganese dissolution.
[0237] In some embodiments, the positive electrode film layer comprises a first sub-positive electrode film layer and a second sub-positive electrode film layer stacked in sequence; the first sub-positive electrode film layer is located on at least one side of the positive electrode current collector; the second sub-positive electrode film layer is located on the side of the first sub-positive electrode film layer away from the positive electrode current collector; the first sub-positive electrode film layer comprises a first lithium manganese iron phosphate and a first carbon nanotube, the molar percentage content of manganese element in the first lithium manganese iron phosphate is Y1, 80%<Y1<100%; the mass percentage content of the first carbon nanotube in the first sub-positive electrode film layer is W1, 0.5%<W1≤1%;
[0238] The second sub-positive electrode film layer comprises a second lithium manganese iron phosphate and a second carbon nanotube, wherein the molar percentage content of the manganese element in the second lithium manganese iron phosphate is Y2, 0<Y2≤20%; the mass percentage content of the second carbon nanotube in the second sub-positive electrode film layer is W2, 0<W2≤0.5%.
[0239] like Figure 7 The positive electrode film layer 22 of the present application includes a first sub-positive electrode film layer 222 and a second sub-positive electrode film layer 221. The first sub-positive electrode film layer 222 has a molar percentage content of manganese in the first lithium manganese iron phosphate greater than the molar percentage content of manganese in the second lithium manganese iron phosphate. Specifically, the molar percentage content of manganese in the first lithium manganese iron phosphate is Y1, which satisfies: 80% < Y1 < 100%, and the molar percentage content of manganese in the second lithium manganese iron phosphate is Y2, 0 < Y2 ≤ 20%; according to the above description In this way, the conductivity of the second positive electrode active material in the second region far away from the positive electrode current collector is stronger than the conductivity of the first positive electrode active material in the first region close to the positive electrode current collector, which is beneficial to improving the phenomenon of poor conductivity in the positive electrode film layer region far away from the positive electrode current collector. On this basis, the first positive electrode active material in the first region is used in combination with a larger amount of carbon nanotubes than the second positive electrode active material in the second region, which is beneficial to further improve the conductivity of the entire positive electrode film layer and evenly distribute it in various regions, so as to improve the conductivity of the electrode sheet and reduce the DC resistance of the battery.
[0240] The numerical ranges of the molar percentage content of manganese element in lithium manganese iron phosphate and the mass percentage content of carbon nanotubes in each sub-positive electrode film layer given in this application are the characteristics of the raw materials added when preparing the positive electrode film layer or are calculated or converted after reasonable regulation. This application ignores the loss or change.
[0241] In these embodiments, the present application provides that the molar percentage content of manganese element in the first lithium manganese iron phosphate is 80.5%, 81%, 81.5%, 82%, 82.5%, 83%, 83.5%, 84%, 84.5%, 85%, 85.5%, 86%, 86.5%, 87%, 87.5%, 88%, 88.5%, 89%, 89.5%, 90%, 90.5%, 91.5%, 92.5%, 93.5%, 94.5%, 95.5%, 96.5%, 97.5%, 98.5%, 99.5%, 100.5%, 101.5%, 102.5%, 103.5%, 104.5%, 105.5%, 106.5%, 107.5%, 108.5%, 109.5%, 110.5%, 111.5%, 112.5%, 113.5%, 114.5%, 115.5%, 116.5%, 117.5%, 118.5%, 119. Any one of 1%, 91.5%, 92%, 92.5%, 93%, 93.5%, 94%, 94.5%, 95%, 95.5%, 96%, 96.5%, 97%, 97.5%, 98%, 98.5%, 99%, 99.5%, 99.6%, 99.7%, 99.8%, 99.9%, 99.99% or any one of the numerical ranges between any two of the above.
[0242] In these embodiments, the present application provides that the molar percentage content of manganese element in the second lithium manganese iron phosphate is Y2 is 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, 7.5% and so on. %, 8.0%, 8.5%, 9.0%, 9.5%, 10.0%, 10.5%, 11.0%, 11.5%, 12.0%, 12.5%, 13.0%, 13.5%, 14.0%, 14.5%, 15.0%, 15.5%, 16.0%, 16.5%, 17.0%, 17.5%, 18.0%, 18.5%, 19.0%, 19.5%, 19.6%, 19.7%, 19.8%, 19.9%, or any one of the numerical ranges between any two of the above.
[0243] In these embodiments, the present application gives the mass percentage content of the first carbon nanotube in the first sub-positive electrode film layer as W1, which is 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, 0.60%, 0.61%, 0.62%, 0.65%, 0.70%, 0.75%, 0.80%, 0.85%, 0.90%, 0.95%, 0.96%, 0.97%, 0.98%, 0.99% or any one of the numerical ranges between any two of the above.
[0244] In these embodiments, the present application provides that the mass percentage content W2 of the second carbon nanotube in the second sub-positive electrode film layer is any one of 0.05%, 0.1%, 0.15%, 0.20%, 0.25%, 0.30%, 0.35%, 0.40%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49% or any one of the numerical ranges between any two of the above.
[0245] In some embodiments, the positive electrode film layer comprises a first sub-positive electrode film layer, a third sub-positive electrode film layer and a second sub-positive electrode film layer stacked in sequence; the first sub-positive electrode film layer is located on at least one side surface of the positive electrode current collector; the second sub-positive electrode film layer is located on the side surface of the first sub-positive electrode film layer away from the positive electrode current collector; the third sub-positive electrode film layer is located between the first sub-positive electrode film layer and the second sub-positive electrode film layer; the first sub-positive electrode film layer comprises a first lithium manganese iron phosphate and a first carbon nanotube, the molar percentage content of manganese element in the first lithium manganese iron phosphate is Y1, 60%<Y1<100%; the mass percentage of the first carbon nanotube in the first sub-positive electrode film layer is The molar content of manganese in the third lithium manganese iron phosphate is Y3, 20% <Y3 ≤ 60%; the mass percentage of the third carbon nanotube in the third sub-positive electrode film layer is W3, 0.4 <W3 ≤ 0.8%; the second sub-positive electrode film layer comprises a second lithium manganese iron phosphate and a second carbon nanotube, the molar content of manganese in the second lithium manganese iron phosphate is Y2, 0 <Y2 ≤ 20%; the mass percentage of the second carbon nanotube in the second sub-positive electrode film layer is W2, 0 <W2 ≤ 0.4%.
[0246] like Figure 8 The positive electrode film layer 22 of the present application includes a first sub-positive electrode film layer 222, a third sub-positive electrode film layer 223 and a second sub-positive electrode film layer 221, and along the stacking direction of the pole pieces (coordinate axis x direction), the molar percentage content of the manganese element in the lithium manganese iron phosphate changes successively. Similarly, the mass percentage content of the carbon nanotubes also changes successively. On the one hand, this design method is conducive to improving the uniform distribution of the conductivity of the entire positive electrode film layer in various regions to improve the conductivity of the pole piece to reduce the DC resistance of the battery. On the other hand, it makes the second region away from the positive electrode collector less prone to manganese dissolution than the first region close to the positive electrode collector, thereby improving the cycle or storage stability of the battery.
[0247] In these embodiments, the present application provides that the molar percentage content of manganese element in the first lithium manganese iron phosphate is 60.1%, 60.5%, 61.0%, 61.1%, 61.5%, 62.0%, 62.1%, 62.5%, 63.0%, 63.1%, 63.5%, 64.0%, 64.1%, 64.5%, 65.0%, 65.1%, 65.5%, 66.0%. , 66.1%, 66.5%, 67.0%, 67.5%, 68.0%, 68.5%, 69.0%, 69.5%, 70.0%, 70.5%, 71.0%, 71.5%, 72.0%, 72.5%, 73.0%, 73.5%, 74.0%, 74.5%, 75.0%, 75.5%, 76.0%, 76.5%, 77.0%, 77.5% , 78.0%, 78.5%, 79.0%, 79.5%, 80.0%, 80.5%, 81.0%, 81.5%, 82.0%, 82.5%, 83.0%, 83.5%, 84%, 84.5%, 85%, 85.5%, 86%, 86.5%, 87%, 87.5%, 88%, 88.5%, 89%, 89.5%, 90%, 90.5%, 91.5%, 92. Any one of 1%, 91.5%, 92%, 92.5%, 93%, 93.5%, 94%, 94.5%, 95%, 95.5%, 96%, 96.5%, 97%, 97.5%, 98%, 98.5%, 99%, 99.5%, 99.6%, 99.7%, 99.8%, 99.9%, 99.99% or any one of the numerical ranges between any two of the above.
[0248] In these embodiments, the present application provides that the molar percentage content of manganese element in the third lithium manganese iron phosphate is Y3 of 20.1%, 20.5%, 21.0%, 21.5%, 22.0%, 22.5%, 23.0%, 23.5%, 24.0%, 24.5%, 25.0%, 25.5%, 26.0%, 26.5%, 27.0%, 27.5%, 28.0%. , 28.5%, 29.0%, 29.5%, 30.0%, 30.5%, 31.0%, 31.5%, 32.0%, 32.5%, 33.0%, 33.5%, 34.0%, 34.5%, 35.0%, 35.5%, 36.0%, 36.5%, 37.0%, 37.5%, 38.0%, 38.5%, 39.0%, 39.5%, 40.0%, 40.5%, 41.0%, 41.5%, 42.0%, 42.5%, 43.9%, 43.5%, 44.0%, 44.5%, 45.0%, 45.5%, 46.0%, 46.5%, 47.0%, 47.5%, 48.0%, 48.5%, 49.0%, 49.5%, 50.0%, 50.5%, 51.0%, Any one of 51.5%, 52.0%, 52.5%, 53.0%, 53.5%, 54.0%, 54.5%, 54.5%, 55.0%, 55.5%, 56.0%, 56.5%, 57.0%, 57.5%, 58.0%, 58.5%, 59.0%, 59.5%, 59.9% or any one of the numerical ranges between any two of the above.
[0249] In these embodiments, the present application provides that the molar percentage content of manganese element in the second lithium manganese iron phosphate is Y2 is 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, 7.5% and so on. %, 8.0%, 8.5%, 9.0%, 9.5%, 10.0%, 10.5%, 11.0%, 11.5%, 12.0%, 12.5%, 13.0%, 13.5%, 14.0%, 14.5%, 15.0%, 15.5%, 16.0%, 16.5%, 17.0%, 17.5%, 18.0%, 18.5%, 19.0%, 19.5%, 19.6%, 19.7%, 19.8%, 19.9%, or any one of the numerical ranges between any two of the above.
[0250] In these embodiments, the present application provides that the mass percentage content W1 of the first carbon nanotube in the first sub-positive electrode film layer is any one of 0.81%, 0.85%, 0.90%, 0.95%, 0.96%, 0.97%, 0.98%, 0.99% or any one of the numerical ranges between any two of the above.
[0251] In these embodiments, the present application gives the mass percentage content W3 of the third carbon nanotube in the third sub-positive electrode film layer as any one of 0.41%, 0.45%, 0.50%, 0.51%, 0.55%, 0.60%, 0.65%, 0.70%, 0.75%, 0.80% or any one of the numerical ranges between any two of the above.
[0252] In these embodiments, the present application provides that the mass percentage content W2 of the second carbon nanotube in the second sub-positive electrode film layer is any one of 0.01%, 0.05%, 0.1%, 0.15%, 0.20%, 0.25%, 0.30%, 0.35%, 0.40% or any one of the numerical ranges between any two of the above.
[0253] In some embodiments, the positive electrode film layer further comprises any one or more of carbon black and graphene;
[0254] The specific surface area of the carbon black is ≥100m 2 / g.
[0255] In some embodiments, the number of graphene layers is 1 to 10, and the average sheet diameter of each layer is 2 μm to 8 μm.
[0256] In some embodiments, the mass percentage of the carbon black and / or graphene in the positive electrode film layer is 0 to 2.5%.
[0257] The graphene of the present application is a kind of sp 2 A single-layer carbon nanomaterial composed of hybridized carbon atoms has a sheet-like structure and good electron mobility.
[0258] The graphene sheet structure of the present application can be a single sheet or two or more sheets stacked together. The method for measuring the number of graphene layers includes any conventional method in the art, such as selecting the application area to be tested, using a projection electron microscope + electron diffraction method to determine the number of layers of the sample by changing the direction of the electron beam incident on the graphene and the change law of the intensity of the graphene diffraction spots under different electron beam incident angles.
[0259] The sheet diameter of each layer in the present application refers to the lateral size of the graphene sheet structure, wherein the average sheet diameter is the average of the sheet diameters of each layer, obtained by high-power electron microscope observation and measurement. The average measurement method here is any conventional method in the art.
[0260] The average sheet diameter of the graphene in the present application is 2 μm to 8 μm, so as to be easily coated on a part of the surface of the positive electrode active material, thereby directly improving the conductivity of the positive electrode active material.
[0261] The present application discloses in these embodiments that the average flake diameter of each layer is any one of 2 μm, 2.5 μm, 3 μm, 4 μm, 4.5 μm, 5 μm, 6 μm, 7.8 μm or any one of the values within any two ranges above.
[0262] The definition and measurement method of the specific surface area of carbon black in the present application are consistent with those of the above-mentioned carbon nanotubes, and are not elaborated herein.
[0263] The carbon black of the present application has a large specific surface area, which is also beneficial to increase the contact between the carbon black and the positive electrode active material, thereby improving the conductivity of the positive electrode sheet.
[0264] In some embodiments, the carbon black has a BET surface area of 100 m 2 / g~1000m 2 / g.
[0265] The specific surface area of carbon black given in these examples is BET 100 m 2 / g~150m 2 / g, 120m 2 / g~180m 2 / g, 150m 2 / g~250m 2 / g, 180m 2 / g~300m 2 / g, 250m 2 / g~400m 2 / g、300m 2 / g~450m 2 / g, 400m 2 / g~500m 2 / g, 450m 2 / g~550m 2 / g、500m 2 / g~600m 2 / g, 550m 2 / g~700m 2 / g, 600m 2 / g~800m 2 / g, 650m 2 / g~1000m 2 / g or any of the values satisfying any two of the above ranges.
[0266] In the present application, the conductive agent in the positive electrode film layer may only include carbon nanotubes with a one-dimensional tubular structure, and may also include one or two of carbon black and graphene, wherein graphene has a flake structure and carbon black has a dot structure. In some embodiments of the present application, a conductive agent is selected for use in combination, such as one-dimensional tubular structure + flake structure graphene + dot-shaped carbon black, which is beneficial to improve the conductivity of the positive electrode plate by constructing a conductive network.
[0267] The present application discloses in some embodiments that the mass percentage content of carbon black in the above-mentioned positive electrode film layer is 0 to 2.5%.
[0268] The present application discloses in some embodiments that the mass percentage content of graphene in the above-mentioned positive electrode film layer is 0-2.5%.
[0269] The present application discloses in some embodiments that the total amount of carbon black and graphene in the positive electrode film layer has a mass percentage of 0 to 2.5%.
[0270] In these embodiments, the present application discloses that the mass percentage content of the above-mentioned components or the total amount in the positive electrode film layer is 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5% or any one of the values satisfying any two of the above ranges.
[0271] In some embodiments, the positive electrode film layer further comprises a dispersant, and the dispersant comprises any one or more of hydrogenated nitrile rubber and its modified compounds, polyvinylidene fluoride and its modified compounds;
[0272] The weight average molecular weight of the hydrogenated nitrile rubber and its modified compound is 50,000 to 150,000.
[0273] In some embodiments, the hydrogenated nitrile rubber and its modified compounds contain structural units derived from acrylonitrile monomers, and the mass percentage content of the structural units derived from acrylonitrile monomers in the hydrogenated nitrile rubber and its modified compounds is 20% to 40%.
[0274] In some embodiments, the degree of hydrogenation of the hydrogenated nitrile rubber and its modified compounds is ≥99%.
[0275] In some embodiments, the weight average molecular weight of the polyvinylidene fluoride and its modified compounds is 2 million to 4 million.
[0276] In some embodiments, the crystallinity of the polyvinylidene fluoride and its modified compounds is 40% to 60%.
[0277] The present application uses carbon nanotubes as a conductive agent in the positive electrode film layer, but the one-dimensional tubular carbon nanotubes are not easily dispersed well and agglomerate, thereby affecting the conductivity. In order to disperse the carbon nanotubes well, the present application selects to add a certain type and a certain amount of dispersant.
[0278] The hydrogenated nitrile rubber of the present application is a product obtained by hydrogenating and saturating the carbon-carbon double bonds on the molecular chain of nitrile rubber, and nitrile rubber is a polymer formed by the polymerization of acrylonitrile and butadiene monomers. The polymer of the present application refers to a collection of macromolecules that are chemically uniform but different in degree of polymerization, molar mass and chain length prepared by polymerization reaction. The modified compound of hydrogenated nitrile rubber in the present application generally refers to a compound obtained by chemical modification, such as functional group modification of hydrogenated nitrile rubber, and the functional group includes but is not limited to carboxyl, ester group, amide group, etc. The hydrogenated nitrile rubber and its modified compound provided by the present application are improved by the dispersibility of carbon nanotubes to increase the content of conductive agent in the positive electrode film layer, thereby exerting good conductivity.
[0279] The weight average molecular weight of the hydrogenated nitrile rubber and its modified compounds of the present application may be determined by conventional methods in the art, such as gel chromatography.
[0280] In the present application, the hydrogenated nitrile rubber and its modified compounds having a suitable weight average molecular weight are conducive to exerting their good dispersibility.
[0281] In these embodiments, the present application discloses that the weight average molecular weight of hydrogenated nitrile rubber and its modified compounds includes any one or more of 50,000, 55,000, 60,000, 65,000, 70,000, 75,000, 80,000, 85,000, 90,000, 95,000, 100,000, 105,000, 110,000, 112,000, 115,000, 120,000, 125,000, 130,000, 135,000, 140,000, 145,000, and 150,000.
[0282] In some embodiments, the hydrogenated nitrile rubber and its modified compounds contain structural units derived from acrylonitrile monomers, and the mass percentage content of the structural units derived from acrylonitrile monomers is 20% to 40%.
[0283] The hydrogenated nitrile rubber of the present application is a product obtained by further hydrogenating and saturating the carbon-carbon double bonds of a polymer obtained by polymerization of acrylonitrile and butadiene monomers. The modified compound of hydrogenated nitrile rubber generally refers to a mixture obtained by chemical modification, such as functional group modification of hydrogenated nitrile rubber, and the functional groups include but are not limited to carboxyl, ester, amide, etc. As mentioned above, after the qualitative and quantitative tests of hydrogenated nitrile rubber and its modified compounds in the pole piece, it is convenient to calculate the mass percentage content of acrylonitrile.
[0284] The present application discloses in these embodiments that the mass percentage content of acrylonitrile in hydrogenated nitrile rubber and its modified compounds includes any one or more of 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, and 40%.
[0285] In some embodiments, the degree of hydrogenation of the hydrogenated nitrile rubber and its modified compounds is ≥99%.
[0286] The hydrogenated nitrile rubber of the present application is obtained by further hydrogenating the carbon-carbon double bonds after polymerization of acrylonitrile and butadiene monomers. Therefore, the degree of hydrogenation here also refers to the hydrogenation saturation. The determination method includes measuring the residual double bonds by infrared spectrometer and calculating the double bond content. The degree of hydrogenation is (100% - double bond content). Alternatively, it can be determined by nuclear magnetic resonance hydrogen spectrometer.
[0287] In the present application, the hydrogenated nitrile rubber and its modified compounds have a higher degree of hydrogenation, and the flexibility of the molecules is better, and the dispersibility to carbon nanotubes is also better.
[0288] The polyvinylidene fluoride of the present application includes structural units derived from vinylidene fluoride. In addition to structural units derived from vinylidene fluoride, the polyvinylidene fluoride and its modified compounds of the present application also include other structural units, including but not limited to acrylic monomer structural units.
[0289] In the present application, the weight average molecular weight of polyvinylidene fluoride and its modified compounds can be tested by methods known in the art, such as gel chromatography, such as Waters 2695Isocratic HPLC gel chromatograph (differential refractive index detector 2141). In some embodiments, the test method is to use a certain mass fraction of polystyrene solution sample as a reference, and select a matching chromatographic column (oily: Styragel HT5DMF7.8*300mm+Styragel HT4). Use purified nitrogen methyl pyrrolidone (NMP) solvent to prepare a certain mass fraction of polyvinylidene fluoride and its modified compound glue, and the prepared solution is allowed to stand for one day for standby use. During the test, tetrahydrofuran is first drawn with a syringe, rinsed, and repeated several times. Then draw 5ml of experimental solution, remove the air in the syringe, and wipe the needle tip dry. Finally, slowly inject the sample solution into the injection port. After the reading is stable, obtain data and read the weight average molecular weight.
[0290] The present application selects polyvinylidene fluoride and its modified compounds with a weight average molecular weight of 2 million to 4 million as dispersants for dispersing carbon nanotubes, which is beneficial to improving dispersibility.
[0291] In these embodiments, the present application provides that the weight average molecular weight of polyvinylidene fluoride and its modified compounds is any one of 2 million, 2.5 million, 3 million, 3.5 million, 4 million or any one of the values satisfying any two of the above ranges.
[0292] In the present application, the crystallinity of polyvinylidene fluoride and its modified compounds refers to the proportion of the crystalline region in the compound. There are some regions with stable and regular arrangement of molecules in the microstructure, and the region with regular and close arrangement of molecules is called the crystalline region.
[0293] In the present application, the crystallinity test can be tested by methods known in the art, such as differential scanning calorimetry. In some embodiments, 0.5 g of polyvinylidene fluoride and its modified compounds are placed in an aluminum dry pan, shaken flat, covered with a crucible lid, and in a nitrogen atmosphere, with a purge gas of 50 ml / min, a protective gas of 70 mL / min, a heating rate of 8 ° C / min, and a test temperature range of 30 ° C to 200 ° C, using a differential scanning calorimeter (DSC) of the German Netzsch company with an instrument model of DSC 200F30 to test and eliminate the thermal history.
[0294] This test will obtain the DSC / (Mw / mg) curve of polyvinylidene fluoride and its modified compounds versus temperature, and integrate it. The peak area is the melting enthalpy ΔH (J / g) of polyvinylidene fluoride and its modified compounds. Crystallinity = ΔH / (ΔHm100%)*100%, where ΔHm100% is the standard melting enthalpy (crystalline melting heat) of the compound, ΔHm100% = 104.7 J / g.
[0295] The compound having a crystallinity within the above range can improve the dispersion of carbon nanotubes at a low addition amount and reduce the battery impedance.
[0296] In these embodiments, the present application provides that the crystallinity of polyvinylidene fluoride and its modified compounds is any one of 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60% or any one of the values satisfying any two of the above ranges.
[0297] In some embodiments, the film resistance of the positive electrode sheet is less than or equal to 1Ω.
[0298] In some embodiments, the film resistance of the positive electrode sheet is 0.1Ω to 1Ω.
[0299] The diaphragm resistance in the present application can be used to measure the conductivity of the electrode. The test of the diaphragm resistance of the positive electrode of the present application can be carried out by methods known in the art, such as the four-probe method. The positive electrode is cut into 3*3mm small discs along the left, middle and right sides by the Yuanneng Technology electrode resistance meter test device, and placed in the sample placement area of the resistance meter test device, and the device is turned on to measure the resistance value.
[0300] In some embodiments, the particle size of the first positive electrode active material and / or the second positive electrode active material satisfies: Dv50 is 0.5 μm to 1.5 μm.
[0301] In some embodiments, a carbon coating layer is formed on the outer side of particles of the first positive electrode active material and / or the second positive electrode active material, and the thickness of the carbon coating layer is 0.01 μm to 1 μm.
[0302] The particle size Dv50 in this application includes 50% of the volume of particles with a particle size larger than it and 50% of the volume of particles smaller than it, which is also called the median diameter and is usually used to indicate the average particle size of the particles. The volume particle size distribution of this application can be measured by conventional measurement methods in the art, such as using a particle size analyzer to measure the particle size distribution and then obtain it by statistics. This application chooses to refer to the laser diffraction particle size analysis method in these embodiments, specifically refers to the standard GB / T19077-2016 to obtain the particle size distribution diagram, and then obtains it by calculation.
[0303] In these embodiments, the present application provides that the particle size of the first positive electrode active material and / or the second positive electrode active material is any one of 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1.0μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm or any one of the values in the range of any two of the above.
[0304] The carbon coating layer of the present application refers to a substance formed on the outer surface of the positive electrode active material. The carbon coating layer can completely or partially coat the outer surface of the positive electrode active material. Since the carbon coating layer has conductivity, on the one hand, the carbon coating layer is conducive to improving the conductivity of the positive electrode active material. On the other hand, the carbon coating layer can also partially block the probability of manganese dissolved in the positive electrode active material reacting with the external electrolyte, so it can also improve the cycle or storage stability of the battery. The determination and thickness measurement methods of the carbon coating layer of the present application include any conventional methods in the art, such as using a high-power electron microscope.
[0305] In these embodiments, the present application provides the thickness of the carbon coating layer as any one of 0.01μm, 0.02μm, 0.03μm, 0.04μm, 0.05μm, 0.06μm, 0.07μm, 0.08μm, 0.09μm, 0.1μm, 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1μm or any one of the values satisfying any two of the above ranges.
[0306] In some embodiments, a distance H between the first surface and the second surface is 0.1 mm to 0.2 mm.
[0307] The present application discloses in the above embodiments that the thickness of the single-side film layer of the positive electrode plate is between 0.1 mm and 0.2 mm.
[0308] [Positive electrode]
[0309] According to some embodiments of the present application, as described above, the positive electrode plate comprises a positive electrode current collector and a positive electrode film layer located on at least one side of the positive electrode current collector, wherein the positive electrode film layer comprises a positive electrode active material.
[0310] The structure and composition of the positive electrode film layer of the present application are as described above, and will not be elaborated herein.
[0311] In some embodiments of the present application, the compaction density of the positive electrode film layer is 2.8 g / cm 3 ~3.4g / cm 3 .
[0312] The compacted density of the positive electrode film layer of the present application can be used to characterize the energy density of the material, the compacted density of the positive electrode film layer = the surface density of the positive electrode film layer / the thickness of the positive electrode film layer, the thickness of the positive electrode film layer includes the distance between the two end faces of the positive electrode film layer along the thickness direction, the surface density of the positive electrode film layer = the weight of the single-sided positive electrode film layer / the area of the single-sided positive electrode film layer, wherein the weight of the single-sided positive electrode film layer can be obtained by weighing, and the area of the single-sided positive electrode film layer can be obtained by using the area calculation formula according to the shape of the film layer.
[0313] In some embodiments of the present application, the positive electrode film layer includes, in addition to the above-mentioned positive electrode active material, conductive agent, and dispersant, a binder, and the binder includes but is not limited to polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, fluorine-containing acrylate resin, styrene-butadiene rubber, polyacrylic acid, sodium polyacrylate, polyacrylamide, polyvinyl alcohol, sodium alginate, polymethacrylic acid, carboxymethyl chitosan, etc., or a combination of two or more thereof.
[0314] The method for forming the positive electrode film layer of the present application comprises mixing the above raw materials with a solvent (such as nitrogen methyl pyrrolidone) in a certain mass ratio to form a positive electrode slurry, and evenly coating the positive electrode slurry on both sides of the positive electrode current collector; controlling the single-side coating weight to be 0.25g-0.50g / 1540.25mm 2 After drying, the cold press is used to compact the material to a certain density (2.8 g / cm 3 ~3.4g / cm 3 ), that is, a positive electrode sheet including a positive electrode film layer is obtained.
[0315] [Negative electrode]
[0316] The negative electrode sheet of the present application includes a negative electrode current collector and a negative electrode film layer located on one side surface or both sides surface of the negative electrode current collector. Generally speaking, the negative electrode film layer is located on both sides surface of the negative electrode current collector, and the formation method includes coating or deposition. The present application will take both sides as an example in the following.
[0317] The present application discloses in some embodiments that the compaction density of the negative electrode film layer is ≥1.65 g / cm 3 .
[0318] In the present application, the compaction density of the negative electrode film layer can be used to characterize the energy density of the material, except that the compaction density of the negative electrode film layer is used to evaluate the compaction density of the negative electrode plate as a whole. The compaction density of the negative electrode film layer = the surface density of the negative electrode film layer / the thickness of the negative electrode film layer. The thickness of the negative electrode film layer includes the distance between the two end faces of the negative electrode film layer along the thickness direction. The surface density of the negative electrode film layer = the weight of the single-sided positive electrode film layer / the area of the single-sided positive electrode film layer. The weight of the single-sided positive electrode film layer can be obtained by weighing, and the area of the single-sided negative electrode film layer can be obtained by using the area calculation formula based on the shape of the film layer. The present application lists in these embodiments that the compaction density of the negative electrode film layer is ≥1.65g / cm 3 .
[0319] The present application discloses in some embodiments that the negative electrode film layer includes a negative electrode active material, and the active material includes one or more of a carbonaceous material, a silicon-based material, a silicon-carbon composite material, a tin-based material and its alloy material. The carbonaceous material in the present application includes one or more of artificial graphite, natural graphite, soft carbon, and hard carbon. Among them, artificial graphite, natural graphite, soft carbon, hard carbon, etc. include materials of any form conventional in the art, and include any conventional manufacturers and models in the art. The silicon-based material in the present application includes one or two of silicon-oxygen materials or silicon-carbon materials, or silicon-carbon composites. The tin-based and alloy materials in the present application include but are not limited to Li-Sn alloys, Li-Sn-O alloys, Sn, SnO, SnO2, etc. And the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for lithium-ion batteries or sodium-ion batteries can also be used. These negative electrode active materials can be used alone or in combination of two or more.
[0320] In some embodiments, the present application discloses that the negative electrode film layer includes a binder and a dispersant, etc. The binder includes but is not limited to polyvinyl alcohol, polyethylene glycol, sodium carboxymethyl cellulose, polyethylene oxide, polyacrylic acid, polyacrylamide, sodium alginate, styrene-butadiene rubber (SBR), etc. The dispersant also includes any conventional type in the art, such as cellulose and its salts, specifically including but not limited to methyl cellulose, carboxymethyl cellulose, hydroxyethyl cellulose, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, etc.
[0321] The method for forming the negative electrode film layer of the present application includes mixing the above-mentioned raw materials with a solvent (such as deionized water) in a certain mass ratio to form a negative electrode slurry, defoaming the negative electrode slurry, and then evenly coating the negative electrode slurry on both sides of the negative electrode collector; controlling the single-sided coating weight; drying, and compacting to a certain compaction density using a cold press to obtain a negative electrode sheet containing a negative electrode film layer.
[0322] [Isolator]
[0323] Some embodiments of the present application disclose an isolating element. The present application has no particular limitation on the type of isolating element, and any known porous isolating element with good chemical stability and mechanical stability can be selected.
[0324] In some embodiments, the isolation member includes a base material layer and a coating disposed on the surface of the base material layer; the base material of the base material layer includes one or more of polyethylene, polypropylene, poly(p-phenylene terephthalamide), polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide and polyamide; the coating includes a ceramic coating and / or a polymer coating. The base material layer has a good permeability to lithium ions, which is beneficial to the migration of lithium ions; the surface of the base material layer is provided with a coating, and the coating can further improve the mechanical properties of the isolation membrane. Furthermore, the ceramic particles in the ceramic coating include one or more of SiO2, Al2O3, AlOOH, CaO, TiO2, MgO, ZnO, ZrO2, Mg(OH)2 and BaSO4. Further, the polymer material of the polymer coating includes one or more of polyethylene (PE), polypropylene (PP), polyphenylene terephthalamide (PPTA), polyethylene terephthalate (PET), polytetrafluoroethylene (PTFE), polyacrylonitrile (PAN), polyimide (PI) and polyamide (PA). The polymer coating and the base material layer can be selected from the same or different materials, and the thickness of the polymer coating and the base material layer can be different. Optionally, the thickness of the polymer coating is less than the thickness of the base material layer.
[0325] In other embodiments, the material of the spacer can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The spacer can be a single-layer film or a multi-layer composite film, without particular limitation. When the spacer is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0326] [Electrolyte]
[0327] In some embodiments of the present application, an electrolyte is disclosed. The electrolyte of the present application may be in liquid, solid, or gel state. Among them, the solid state is a solid electrolyte, the liquid state is a liquid electrolyte, and the gel state is a gel electrolyte. The secondary battery of the present application uses a liquid electrolyte, that is, an electrolyte. The electrolyte contains an electrolyte salt and an organic solvent. Among them, the types of electrolyte salts include any conventional types in the art, for example, including but not limited to inorganic metal salts, such as RClO4, RAsF6, RPF6, RBF4, RSbF6, RSO3F, RN(FSO2)2, etc.; fluorine-containing organic metal salts, such as RCF3SO3, RN(FSO2)(CF3SO2), RN(CF3SO2)2, RN(C2F5SO2)2, cyclic 1,3-hexafluoropropane disulfonyl imide lithium, cyclic 1,2-tetrafluoroethane disulfonyl imide lithium, RN(CF3SO2)(C4F9S O2), RC(CF3SO2)3, RPF4(CF3)2, RPF4(C2F5)2, RPF4(CF3SO2)2, RPF4(C2F5SO2)2, RBF2(CF3)2, RBF2(C2F5)2, RBF2(CF3SO2)2, RBF2(C2F5SO2)2, etc.; and metal salts containing dicarboxylic acid complexes, such as lithium bis(oxalato)borate, lithium difluorooxalatoborate, lithium tris(oxalato)phosphate, lithium difluorobis(oxalato)phosphate, lithium tetrafluoro(oxalato)phosphate, etc. The metal and R here both contain lithium ions.
[0328] According to some embodiments of the present application, the concentration of the electrolyte salt in the electrolyte is 0.1mol / L to 4mol / L. The present application discloses in these embodiments that the concentration of the electrolyte salt is 0.1mol / L, 0.2mol / L, 0.3mol / L, 0.4mol / L, 0.5mol / L, 0.6mol / L, 0.7mol / L, 0.8mol / L, 0.9mol / L, 1mol / L, 1.2mol / L, 1.5mol / L, 1.8mol / L, 2mol / L, 2.2mol / L, 2.5mol / L, 2.8mol / L, 3mol / L, 3.2mol / L, 3.5mol / L, 3.8mol / L, 4mol / L, or any one of the values satisfying the above range.
[0329] As mentioned above, the organic solvent includes any one or more of carboxylic acid ester compounds, carbonate compounds, and ether compounds. Among them, the carboxylic acid ester compounds include one or more of ethyl acetate (EA), methyl acetate (MA), ethyl propionate (EP), propyl acetate (PA), methyl propionate (MP), methyl butyrate (MB), ethyl butyrate (EB), and 1,4-butyrolactone (GBL); the carbonate compounds include one or more of ethylene carbonate (EC), propylene carbonate (PC), vinylene carbonate, dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), ethyl methyl carbonate (EMC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), and fluoroethylene carbonate (FEC). The ether compounds include at least one of tetrahydrofuran, dimethyltetrahydrofuran, tetrahydropyran, dimethyltetrahydropyran, 1,2-dimethoxyethane, dipropylene glycol dimethyl ether, or dimethyl phthalate. The organic solvent of the present application further comprises one or two of nitrile solvents and sulfone solvents, wherein the nitrile solvent comprises one or more of acetonitrile (AN), glutaronitrile (GLN) and adiponitrile (ADN). The sulfone solvent comprises at least one or a combination of two of sulfolane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS) and diethyl sulfone (ESE).
[0330] According to some embodiments of the present application, the electrolyte further comprises a film-forming stabilizer, which comprises a positive electrode film-forming stabilizer and a negative electrode film-forming stabilizer, wherein the positive electrode film-forming stabilizer comprises carbonate additives and / or sulfate additives, and the carbonate additives include one or more of vinylene carbonate (VC), fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), vinyl ethylene carbonate (VEC) and dioctyl carbonate (CC). Sulfate additives include cyclic sulfonate additives and / or alkyl sulfate additives; further, cyclic sulfonate additives include one or more of 1,3-propane sultone (PS), propylene sultone (PES), and 3-fluoro-1,3-propane sultone (FPS); alkyl sulfate additives include one or more of vinyl sulfate (DTD), diethyl sulfate (DES) and dimethyl sulfate (DMS). The negative electrode film-forming stabilizer includes one or more of boron lithium salts, phosphorus-containing lithium salts and sulfur-containing lithium salts; boron-containing lithium salts include one or more of lithium tetrafluoroborate (LiBF4), lithium bis(oxalatoborate) (LiBOB) and lithium bis(fluorooxalatoborate) (LiDFOB); phosphorus-containing lithium salts include one or more of lithium difluorophosphate (LiPO2F2), lithium fluorophosphate (Li2PO3F) and lithium phosphate (Li3PO4). Sulfur-containing lithium salts include one or more of lithium fluorosulfonate (LiFSO3), lithium sulfate (Li2SO4) and lithium sulfamate (LiSO3NH2).
[0331] The secondary battery of the present application will be described in detail below in conjunction with specific embodiments.
[0332] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.
[0333] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0334] Conventional techniques of inorganic chemistry within the art can be used in this application. In the following examples, efforts are made to ensure the accuracy of the numbers used (including amounts, temperatures, reaction times, etc.), but some experimental errors and deviations should be considered. The temperatures (in degrees Celsius) used in the following examples are expressed in ° C, and the pressure is atmospheric pressure or near atmospheric pressure. All pharmaceutical reagents are purchased at AR grade, and all reactions are carried out under argon protection. Unless otherwise noted, all reagents are obtained from commercial channels.
[0335] Experimental materials:
[0336] 1. Lithium iron manganese phosphate, lithium iron phosphate, lithium manganese phosphate: commercially available;
[0337] 2. Carbon nanotubes: Wuxi Dongheng New Energy Technology Co., Ltd.;
[0338] 3. Dispersant - hydrogenated nitrile rubber and its modified compounds: Zeon Co., Ltd.;
[0339] Dispersant-polyvinylidene fluoride and its modified compounds: China Blue Sky Group Co., Ltd.;
[0340] 4. Carbon black: Jiangxi Black Cat Carbon Black Co., Ltd.;
[0341] 5. Graphene: commercially available;
[0342] The performance parameters of some experimental raw materials are listed below:
[0343] Table 1-1 Parameters of positive electrode active materials
[0344]
[0345] Table 1-2 Parameters of carbon nanotubes
[0346]
[0347] Table 1-3 Parameters of carbon black
[0348] Serial number <![CDATA[Specific surface area BET / m 2 / g]]> 3-1 381
[0349] Table 1-4 Parameter list of graphene
[0350] Serial number Number of layers Average flake diameter / μm 4-1 3 5.0
[0351] Table 1-5 Parameters of hydrogenated nitrile rubber
[0352] Serial number Acrylonitrile content (%) Degree of hydrogenation (%) Weight average molecular weight 5-1 34% 99.5% 212386
[0353] Table 1-6 Parameters of polyvinylidene fluoride
[0354] Serial number Crystallinity Weight average molecular weight 6-1 50.2% 2.26 million
[0355] Example 1 (double-layer multiple coating, different single-walled carbon tube contents)
[0356] A secondary battery is provided, which comprises a positive electrode plate, a separator and a negative electrode plate which are stacked in sequence, and also comprises an electrolyte.
[0357] The preparation of the positive electrode sheet comprises the following steps:
[0358] (1) preparing a carbon nanotube dispersion: dispersing the carbon nanotube powder 2-1 and the hydrogenated nitrile rubber 5-1 in nitrogen methyl pyrrolidone to form a carbon nanotube dispersion;
[0359] (2) Preparation of the first positive electrode slurry: Lithium manganese iron phosphate 1-3 (LiFe 0.1 Mn 0.9 O4), the carbon nanotube dispersion and the adhesive styrene-butadiene rubber are mixed together, and nitrogen methyl pyrrolidone solvent is added and stirred to form a first positive electrode slurry;
[0360] (3) Preparation of the second positive electrode slurry: LiFe 1-3 0.1 Mn 0.9 O4), the carbon nanotube dispersion and the adhesive styrene-butadiene rubber are mixed together, and nitrogen methyl pyrrolidone solvent is added and stirred to form a second positive electrode slurry; the difference between the second positive electrode slurry and the first positive electrode slurry is that the amount of carbon nanotube dispersion added is different so that the carbon nanotube content in the first sub-positive electrode film layer and the second sub-positive electrode film layer is different;
[0361] (4) Preparation of positive electrode sheet: coating the first positive electrode slurry on both surfaces of the positive electrode current collector aluminum foil to obtain a first sub-positive electrode film layer, wherein the first sub-positive electrode film layer has LiFe 0.1 Mn 0.9 The mass percentage contents of O4, carbon nanotubes and hydrogenated nitrile rubber are shown in Table 2-1.
[0362] The second positive electrode slurry is coated on both surfaces of the first sub-positive electrode film layer to obtain a second sub-positive electrode film layer, wherein the second sub-positive electrode film layer has LiFe 0.1 Mn 0.9 The mass percentage contents of O4, carbon nanotubes and hydrogenated nitrile rubber are shown in Table 2-1.
[0363] This embodiment also provides that the thickness H of the positive electrode film layer is 0.15 mm, wherein the thickness of the first sub-positive electrode film layer and the second sub-positive electrode film layer are 0.075 mm respectively.
[0364] Preparation of negative electrode sheet:
[0365] Take graphite and conductive agent carbon black, binder styrene butadiene rubber (SBR), thickener sodium carboxymethyl cellulose (CMC-Na) according to the weight ratio of 96.2:1.8:0.8:1.2 and dissolve in solvent deionized water, stir until the system is uniform under the action of a vacuum mixer, and evenly coat the negative electrode slurry on both sides of the negative electrode current collector copper foil. Use a nine-section oven with the temperature settings of 100℃ / 100℃ / 95℃ / 85℃ / 85℃ / 80℃ / 80℃ / 80℃ / 60℃ for drying, and then use a cold press to compact it to obtain a negative electrode sheet.
[0366] Prepare electrolyte:
[0367] In an environment with a water content of less than 10 ppm, non-aqueous organic solvents ethylene carbonate, diethyl carbonate and dimethyl carbonate are mixed in a volume ratio of 1:1:1 to obtain a solvent, and lithium salt lithium hexafluorophosphate is added to the solvent to form an electrolyte with a lithium hexafluorophosphate concentration of 1 mol / L.
[0368] Separation film available:
[0369] A porous polyethylene (PE) film with a thickness of 13 μm was used as the isolation film.
[0370] Preparation of battery cells:
[0371] The positive electrode sheet, the isolation film, and the negative electrode sheet are stacked in order, so that the isolation film is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and the corresponding assembly forms a stacked bare cell; the stacked bare cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a battery cell is obtained.
[0372] Example 1-1 (double-layer single coating, same carbon tube content)
[0373] A secondary battery is provided. The secondary battery is different from Example 1 in that a first positive electrode slurry is coated on two surfaces of a positive electrode current collector aluminum foil to obtain a positive electrode film layer with a thickness of H.
[0374] The other parts of this embodiment 1-1 remain the same as those of embodiment 1.
[0375] Comparative Example 1
[0376] A battery cell is provided, which is different from the above-mentioned embodiment 2-1 in that the positive electrode active material is replaced by lithium manganese phosphate (serial number 1-2 in Table 1-1), and the conductive agent is replaced by carbon black (serial number 3-1 in Table 1-3), and the mass ratio of lithium manganese phosphate, carbon black 3-1, hydrogenated nitrile rubber 5-1 and binder styrene butadiene rubber is 94%:2.5%:1.5%:2%, and the rest is the same as embodiment 2-1.
[0377] Example 2-1 (double-layer multiple coating, different manganese content, different carbon tube content)
[0378] A secondary battery is provided, which is different from the embodiment 1 in that the positive electrode plate is different.
[0379] (1) Preparing a first carbon nanotube dispersion: dispersing the carbon nanotube powder 2-1 and the hydrogenated nitrile rubber 5-1 in nitrogen methyl pyrrolidone to form a first carbon nanotube dispersion;
[0380] (2) preparing a second carbon nanotube dispersion: dispersing the carbon nanotube powder 2-2 and the hydrogenated nitrile rubber 5-1 in nitrogen methyl pyrrolidone to form a second carbon nanotube dispersion;
[0381] (3) Preparation of the first positive electrode slurry: LiFe 1-3 0.1 Mn 0.9 O4), mixing the first carbon nanotube dispersion and the adhesive styrene-butadiene rubber together, adding nitrogen methyl pyrrolidone solvent and stirring to form a first positive electrode slurry;
[0382] (4) Preparation of the second positive electrode slurry: LiFe 1-6 manganese iron phosphate 0.8 Mn 0.2 O4), the second carbon nanotube dispersion and the adhesive styrene butadiene rubber are mixed together, and nitrogen methyl pyrrolidone solvent is added and stirred to form a first positive electrode slurry; the difference between the second positive electrode slurry and the first positive electrode slurry is that the type of positive electrode active material is different and the content of carbon nanotubes is also different.
[0383] (5) Preparation of positive electrode sheet: coating the first positive electrode slurry on both surfaces of the positive electrode current collector aluminum foil to obtain a first sub-positive electrode film layer, wherein the first sub-positive electrode film layer has LiFe 0.1 Mn 0.9 The mass percentage contents of O4, carbon nanotubes and hydrogenated nitrile rubber are shown in Table 2-1.
[0384] The second positive electrode slurry is coated on both surfaces of the first sub-positive electrode film layer to obtain a second sub-positive electrode film layer, wherein the second sub-positive electrode film layer has LiFe 0.8 Mn 0.2The mass percentage contents of O4, carbon nanotubes, and hydrogenated nitrile rubber are shown in Table 2-1. The other parts of Example 2-1 are the same as those of Example 1.
[0385] Example 2-2 (three layers of multiple coatings, different manganese content, different carbon tube content)
[0386] A secondary battery is provided, which is different from the embodiment 1 in that the positive electrode plate is different.
[0387] (1) Preparing a first carbon nanotube dispersion: dispersing the carbon nanotube powder 2-1 and the hydrogenated nitrile rubber 5-1 in nitrogen methyl pyrrolidone to form a first carbon nanotube dispersion;
[0388] (2) preparing a third carbon nanotube dispersion: dispersing the carbon nanotube powder 2-3 and the hydrogenated nitrile rubber 5-1 in nitrogen methyl pyrrolidone to form a third carbon nanotube dispersion;
[0389] (3) preparing a second carbon nanotube dispersion: dispersing the carbon nanotube powder 2-2 and the hydrogenated nitrile rubber 5-1 in nitrogen methyl pyrrolidone to form a second carbon nanotube dispersion;
[0390] (4) Preparation of the first positive electrode slurry: Lithium manganese iron phosphate 1-3 (LiFe 0.1 Mn 0.9 O4), the first carbon nanotube dispersion and the adhesive styrene-butadiene rubber are mixed together, and nitrogen methyl pyrrolidone solvent is added and stirred to form a first positive electrode slurry with a solid content of 60%;
[0391] (5) Preparation of the third positive electrode slurry: Lithium manganese iron phosphate 1-7 (LiFe 0.6 Mn 0.4 O4), a third carbon nanotube dispersion and a binder styrene-butadiene rubber are mixed together, and nitrogen methyl pyrrolidone solvent is added and stirred to form a third positive electrode slurry with a solid content of 60%;
[0392] (4) Preparation of the second positive electrode slurry: LiFe 1-6 manganese iron phosphate 0.8 Mn 0.2 O4), the second carbon nanotube dispersion and the adhesive styrene-butadiene rubber are mixed together, and nitrogen methyl pyrrolidone solvent is added and stirred to form a first positive electrode slurry with a solid content of 60%; the difference between the second positive electrode slurry and the first positive electrode slurry and the third positive electrode slurry is that the types of positive electrode active materials are different, and the types and contents of carbon nanotubes are different.
[0393] (5) Preparation of positive electrode sheet: coating the first positive electrode slurry on both surfaces of the positive electrode current collector aluminum foil to obtain a first sub-positive electrode film layer, wherein the first sub-positive electrode film layer has LiFe 0.1 Mn 0.9The mass percentage contents of O4, carbon nanotubes, hydrogenated nitrile rubber and adhesive are 96.5%, 1.0%, 1.5% and 1.0% respectively.
[0394] The third positive electrode slurry is coated on both surfaces of the first sub-positive electrode film layer to obtain a third sub-positive electrode film layer, wherein the third sub-positive electrode film layer has LiFe 0.6 Mn 0.4 The mass percentage contents of O4, carbon nanotubes, hydrogenated nitrile rubber and adhesive are 96.9%, 0.6%, 1.5% and 1.0% respectively.
[0395] The second positive electrode slurry is coated on the two surfaces of the third sub-positive electrode film layer to obtain the second sub-positive electrode film layer, wherein the second sub-positive electrode film layer has LiFe 0.8 Mn 0.2 The mass percentage contents of O4, carbon nanotubes, and hydrogenated nitrile rubber are 97.2%, 0.3%, 1.5%, and 1.0%, respectively. As shown in Table 2-2, the other parts of this embodiment 2-2 are the same as those of embodiment 1, and the thickness of each sub-positive electrode film layer is 0.05 mm.
[0396] Example 3-1 (double-layer multiple coating, different carbon tube contents, doping)
[0397] A secondary battery is provided, which is different from Example 2-1 in that: the lithium manganese iron phosphate 1-3 (LiFe 0.1 Mn 0.9 O4) is replaced by 1-5 (LiFe 0.05 Mn 0.9 Al 0.05 O4), the other parts of this embodiment are the same as those of embodiment 2-1.
[0398] Example 4-1 (double-layer multiple coating, different carbon tube contents, and carbon coating)
[0399] A secondary battery is provided, which is different from Example 2-1 in that: the lithium manganese iron phosphate 1-3 (LiFe 0.1 Mn 0.9 O4) is replaced by 1-4 in Table 1-1 (the thickness of the carbon coating layer is 0.053 μm), and the other parts of this embodiment remain the same as Example 2-1.
[0400] Example 5-1 (double-layer multiple coating, each layer of conductive agent includes carbon tubes + graphene + carbon black)
[0401] A secondary battery is provided, which is different from Example 2-1 in that the positive electrode plate is different.
[0402] (1) preparing a first conductive agent dispersion: dispersing carbon nanotube powder 2-1, carbon black 3-1, graphene 4-1 and hydrogenated nitrile rubber 5-1 in nitrogen methyl pyrrolidone to form a first conductive agent dispersion;
[0403] (2) preparing a second conductive agent dispersion: dispersing the carbon nanotube powder 2-2, the carbon black 3-1, the graphene 4-1 and the hydrogenated nitrile rubber 5-1 in nitrogen methyl pyrrolidone to form a second conductive agent dispersion;
[0404] (3) Preparation of the first positive electrode slurry: LiFe 1-3 0.1 Mn 0.9 O4), mixing the first conductive agent dispersion and the adhesive styrene-butadiene rubber together, adding nitrogen methyl pyrrolidone solvent and stirring to form a first positive electrode slurry;
[0405] (4) Preparation of the second positive electrode slurry: LiFe 1-6 manganese iron phosphate 0.8 Mn 0.2 O4), the second conductive agent dispersion and the adhesive styrene-butadiene rubber are mixed together, and nitrogen methyl pyrrolidone solvent is added and stirred to form a first positive electrode slurry; the difference between the second positive electrode slurry and the first positive electrode slurry is that the type of positive electrode active material is different, and the type and content of the conductive agent are also different.
[0406] (5) Preparation of positive electrode sheet: coating the first positive electrode slurry on both surfaces of the positive electrode current collector aluminum foil to obtain a first sub-positive electrode film layer, wherein the first sub-positive electrode film layer has LiFe 0.1 Mn 0.9 The mass percentage contents of O4, carbon nanotubes and hydrogenated nitrile rubber are shown in Table 2-1.
[0407] The second positive electrode slurry is coated on both surfaces of the first sub-positive electrode film layer to obtain a second sub-positive electrode film layer, wherein the second sub-positive electrode film layer has LiFe 0.8 Mn 0.2 The mass percentage contents of O4, carbon nanotubes, and hydrogenated nitrile rubber are shown in Table 2-3. The other parts of Example 5-1 are the same as those of Example 2-1.
[0408] Example 6-1 (double-layer multiple coating, replacement of dispersant)
[0409] A secondary battery is provided. The secondary battery is different from Example 2-1 in that the dispersant hydrogenated nitrile rubber 5-1 in the first carbon nanotube dispersion and the second carbon nanotube dispersion is replaced with polyvinylidene fluoride 6-1 in Table 1-6.
[0410] The other parts of this embodiment 6-1 remain the same as those of embodiment 2-1.
[0411] Example 7-1 (double-layer coating, the first layer is lithium manganese phosphate, the second layer is lithium iron phosphate, and the carbon tube content is the same)
[0412] A secondary battery is provided, which is different from that of Example 2-1 in that:
[0413] The positive electrode active material in the first sub-positive electrode film layer is lithium manganese phosphate 1-2 (LiMnO4) shown in Table 1-1; the positive electrode active material in the second sub-positive electrode film layer is lithium iron phosphate 1-1 (LiFeO4) shown in Table 1-1, and the carbon nanotube content in the first sub-positive electrode film layer is the same as that in the second sub-positive electrode film layer.
[0414] The other parts of this embodiment 7-1 remain the same as those of embodiment 2-1.
[0415] Example 7-2 (double-layer coating, the first layer is lithium manganese phosphate, the second layer is lithium iron phosphate, and the carbon tube content is different)
[0416] A secondary battery is provided, which is different from Example 8-1 in that the carbon nanotube content in each sub-positive electrode film layer in the positive electrode plate is different. The other parts of this Example 7-2 are the same as those of Example 7-1.
[0417] The composition and proportion of the positive electrode film layer in the above-mentioned Example 1, Example 1-1, Example 2-1, Example 3-1, Example 4-1, Example 6-1, Example 7-1, and Example 7-2 of the present application are shown in the following Table 2-1.
[0418] Table 2-1 Composition of positive electrode film layer
[0419]
[0420]
[0421] The content of each component in each sub-positive electrode film layer in Table 2-1 of the present application is 100%, and the rest includes a binder and essential components.
[0422] The composition and proportion of the positive electrode film layer in the above-mentioned embodiment 2-2 are shown in the following Table 2-2.
[0423] Table 2-2 Composition of positive electrode film layer
[0424]
[0425] The content of each component in each sub-positive electrode film layer in Table 2-2 of the present application is 100%, and the rest includes a binder and essential components.
[0426] The composition and proportion of the positive electrode film layer in the above-mentioned embodiment 5-1 are shown in the following Table 2-3.
[0427] Table 2-3 Composition of positive electrode film layer
[0428]
[0429] Among them, the total mass percentage of each component in each sub-positive electrode film layer in Table 2-1, Table 2-2 and Table 2-3 is 100%. In addition to the types and contents listed in the table, the others are binders or essential components.
[0430] The test methods for the relevant parameters of each positive electrode sheet in Table 2 are specifically shown as follows:
[0431] ①Test method of membrane resistance:
[0432] Cut the dried positive electrode sheets of the above-mentioned embodiments and comparative examples at the left, middle and right positions within a certain interval and cut them into small discs with a diameter of 10 mm. Turn on the power supply of the Yuanneng Technology electrode sheet resistor meter, place it in the appropriate position of the "probe" of the electrode sheet resistor meter, click the "start" button, and wait for the reading to stabilize before reading. Test two positions of each small disc, and finally calculate the average value of the six measurements, which is the film resistance of the electrode sheet, and obtain Table 2-4.
[0433] Table 2-4 Diaphragm resistance of positive electrode
[0434]
[0435]
[0436] It can be seen from the above examples and comparative example 1 in Tables 2-4 that the combination of positive electrode active materials and carbon nanotubes can significantly reduce the resistance of the positive electrode sheet. In combination with Example 1 and Example 1-1, it can be seen that the more carbon nanotubes are used within a certain range, the more conducive to the conductivity. In combination with Example 1 and Example 2-1, it can be seen that the iron content in the positive electrode active material lithium manganese iron phosphate is within a certain range. The higher the content, the less the demand for carbon nanotubes, but it can still show good conductivity when used in combination with carbon nanotubes. In combination with Examples 3-1 and 4-1, it can be seen that after the positive electrode active material is element-doped and carbon-coated, and then combined with carbon nanotubes, it can also exert good conductivity. This may be related to the fact that carbon nanotubes can adhere to the surface of the positive electrode active material, shortening the electron conduction distance.
[0437] [Battery performance test]
[0438] ②Capacity retention rate of battery after 1000 cycles:
[0439] At 25°C, charge the battery to 3.75V at 1C constant current, then charge at constant voltage to a current of 0.05C (corresponding to 100% SOC). After standing for 5 minutes, discharge the battery to the lower limit of 2.5V (corresponding to 0% SOC) at 1C constant current. Record the discharge capacity at this time, which is the discharge capacity of the first cycle. Perform cyclic charge and discharge tests on the battery according to the above method, and record the discharge capacity after each cycle. Capacity retention rate (%) of battery after 1000 cycles at 25°C = discharge capacity after 1000 cycles / discharge capacity of the first cycle × 100%.
[0440] ③Capacity retention rate of battery (60℃) after 300 days of storage:
[0441] At 25°C, the battery was charged at a constant current of 0.5C to a voltage of 3.75V, and then charged at a constant voltage of 3.75V to a current of 0.05C. After standing for 5 minutes, the battery was discharged at a constant current of 0.5C to a voltage of 2.5V. The discharge capacity at this time was the discharge capacity before storage; the battery was then fully charged with a charging current of 0.5C and stood at 60°C for 300 days. After that, it was taken out and stood at 25°C for 2 hours, and then discharged at a constant current of 0.5C to a voltage of 2.5V. After standing for 5 minutes, it was charged at a constant current of 0.5C to a voltage of 3.75V, and then charged at a constant voltage of 3.75V to a current of 0.05C. After standing for 5 minutes, the battery was discharged at a constant current of 0.5C to a voltage of 2.5V. The discharge capacity at this time was the discharge capacity after storage for 300 days.
[0442] The capacity retention rate of the battery after storage at 60° C. for 300 days=(discharge capacity after storage for 300 days / discharge capacity before storage)×100%.
[0443] According to the above test method, the test results shown in Table 3 below are obtained.
[0444] Table 3 Battery performance list
[0445]
[0446]
[0447] Combining Table 2-4 with Table 3, it can be seen that the design method of using different film layers provided by the present application with different positive electrode active materials and carbon nanotubes is conducive to improving the conductivity of the pole piece to reduce the DC resistance of the battery, and ultimately improve the battery performance. Further combining Example 2-1, Example 2-2 and Example 1 in Table 3, it can be seen that the design method of using different film layers provided by the present application with different positive electrode active materials and carbon nanotubes is conducive to improving the cycle stability and storage stability of the battery to a certain extent, which may be due to the reduction of manganese dissolution to a certain extent.
[0448] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.
Claims
1. A battery cell, characterized in that: It includes a positive electrode sheet and a negative electrode sheet which are stacked; The positive electrode sheet comprises a positive electrode current collector and a positive electrode film layer located on at least one side surface of the positive electrode current collector; The positive electrode film layer has a first surface away from the positive electrode current collector and a second surface arranged opposite to the first surface; The distance between the first surface and the second surface is H; Along the stacking direction of the electrode sheets, the area extending from the second surface of the positive electrode film layer to the position of 0.1×H is recorded as the first area of the positive electrode film layer; Along the stacking direction of the electrode sheets, the area extending from the first surface of the positive electrode film layer to the position of 0.1×H is recorded as the second area of the positive electrode film layer; The first region includes a first positive electrode active material and a first carbon nanotube, and the second region includes a second positive electrode active material and a second carbon nanotube; The first positive electrode active material includes any one or more of lithium iron manganese phosphate and lithium manganese phosphate; The second positive electrode active material includes any one or more of lithium manganese iron phosphate and lithium iron phosphate.
2. The battery cell according to claim 1, characterized in that: The mass percentage content of the first carbon nanotubes in the first region is W1; the mass percentage content of the second carbon nanotubes in the second region is W2; W1≥W2.
3. The battery cell according to any one of claims 1 to 2, characterized in that: The mass percentage content of the first carbon nanotubes in the first region is W1 which satisfies: 0<W1≤1%; The mass percentage content of the second carbon nanotubes in the second region is W2 which satisfies: 0<W2≤1%.
4. The battery cell according to any one of claims 1 to 3, characterized in that: The first carbon nanotubes or the second carbon nanotubes each independently include any one or more of single-walled carbon nanotubes or multi-walled carbon nanotubes.
5. The battery cell according to any one of claims 1 to 4, characterized in that: The first carbon nanotubes include single-walled carbon nanotubes; the single-walled carbon nanotubes satisfy any one or more of the following properties: The average tube length is greater than 50μm; the aspect ratio is 10-20; the specific surface area is 800m 2 / g~1600m 2 / g; and / or; The second carbon nanotubes include multi-walled carbon nanotubes; the multi-walled carbon nanotubes satisfy any one or more of the following properties: The average tube length is 5μm to 50μm; the aspect ratio is 1.2 to 2.0; the specific surface area is 170m 2 / g~220m 2 / g.
6. The battery cell according to any one of claims 1 to 5, characterized in that: The first positive electrode active material includes any one or more of lithium iron manganese phosphate and lithium manganese phosphate; The second positive electrode active material includes lithium iron phosphate.
7. The battery cell according to any one of claims 1 to 6, characterized in that: The chemical formula of the lithium manganese iron phosphate is: Li a N b Fe x Mn y M 1-x-y P 1-m Q m O 4-n R n ; Wherein, N represents a lithium doping element, and the lithium doping element includes any one or more of Zn, Al, Na, K, Mg, Nb, Mo and W; M represents a doping element at the manganese position and the iron position, and the doping element at the manganese position and the iron position includes any one or more of Al, Cu, Mg, Zn, Ni, Ti, V, Zr, Co, Ga, Sn, Sb, and Nb; Q represents a doping element at the phosphorus site, and the doping element at the phosphorus site includes any one or more of B, S, Si and N; R represents an oxygen doping element, and the oxygen doping element includes any one or more of S, F, Cl and Br; a is 0.9 to 1.1; b is 0 to 0.1; x is 0.001 to 0.999; y is 0.001 to 0.999; 1-xy is 0 to 0.1; m is 0 to 0.1; n is 0 to 0.
1.
8. The battery cell according to claim 7, characterized in that: The doping elements at the manganese and iron positions include any one or more of Al, Mg, and Ni; 1-xy is 0.01 to 0.
1.
9. The battery cell according to any one of claims 7 to 8, characterized in that: The first positive electrode active material includes a first lithium manganese iron phosphate, and the molar percentage content of manganese element in the first lithium manganese iron phosphate is Y1; The second positive electrode active material includes a second lithium manganese iron phosphate, and the molar percentage content of manganese element in the second lithium manganese iron phosphate is Y2; Y1 ≥ Y2; The Y1 or Y2 is each independently selected from y×100%.
10. The battery cell according to any one of claims 7 to 9, characterized in that: The positive electrode film layer comprises a first sub-positive electrode film layer and a second sub-positive electrode film layer stacked in sequence; The first sub-positive electrode film layer is located on at least one side surface of the positive electrode current collector; The second positive electrode film layer is located on a surface of the first positive electrode film layer that is away from the positive electrode current collector; The first positive electrode film layer comprises a first lithium manganese iron phosphate and a first carbon nanotube, wherein the molar percentage content of manganese element in the first lithium manganese iron phosphate is Y1, 80%<Y1<100%; the mass percentage content of the first carbon nanotube in the first positive electrode film layer is W1, 0.5%<W1≤1%; The second sub-positive electrode film layer includes a second lithium manganese iron phosphate and a second carbon nanotube. The molar percentage content of manganese element in the second lithium manganese iron phosphate is Y2, 0<Y2≤20%; the mass percentage content of the second carbon nanotube in the second sub-positive electrode film layer is W2, 0<W2≤0.5%.
11. The battery cell according to any one of claims 7 to 9, characterized in that: The positive electrode film layer comprises a first sub-positive electrode film layer, a third sub-positive electrode film layer and a second sub-positive electrode film layer stacked in sequence; The first sub-positive electrode film layer is located on at least one side surface of the positive electrode current collector; The second positive electrode film layer is located on a surface of the first positive electrode film layer that is away from the positive electrode current collector; The third sub-positive electrode film layer is located between the first sub-positive electrode film layer and the second sub-positive electrode film layer; The first positive electrode film layer comprises a first lithium manganese iron phosphate and a first carbon nanotube, wherein the molar percentage content of manganese element in the first lithium manganese iron phosphate is Y1, 60%<Y1<100%; the mass percentage content of the first carbon nanotube in the first positive electrode film layer is W1, 0.8%<W1≤1%; The third sub-positive electrode film layer comprises a third lithium manganese iron phosphate and a third carbon nanotube, wherein the molar percentage content of manganese element in the third lithium manganese iron phosphate is Y3, 20%<Y3≤60%; the mass percentage content of the third carbon nanotube in the third sub-positive electrode film layer is W3, 0.4<W3≤0.8%; The second sub-positive electrode film layer includes a second lithium manganese iron phosphate and a second carbon nanotube. The molar percentage content of manganese element in the second lithium manganese iron phosphate is Y2, 0<Y2≤20%; the mass percentage content of the second carbon nanotube in the second sub-positive electrode film layer is W2, 0<W2≤0.4%.
12. The battery cell according to any one of claims 1 to 11, characterized in that: The positive electrode film layer further comprises any one or more of carbon black and graphene; The specific surface area of the carbon black is ≥100m 2 / g; and / or; The number of graphene layers is 1 to 10, and the average sheet diameter of each layer is 2 μm to 8 μm; and / or; The mass percentage content of the carbon black and / or graphene in the positive electrode film layer is 0-2.5%.
13. The battery cell according to any one of claims 1 to 12, characterized in that: The positive electrode film layer further comprises a dispersant, and the dispersant comprises any one or more of hydrogenated nitrile rubber and its modified compounds, polyvinylidene fluoride and its modified compounds; The weight average molecular weight of the hydrogenated nitrile rubber and its modified compounds is 50,000 to 150,000; and / or; The hydrogenated nitrile rubber and its modified compound contain structural units derived from acrylonitrile monomers, and the mass percentage content of the structural units derived from acrylonitrile monomers in the hydrogenated nitrile rubber and its modified compound is 20% to 40%; and / or; The degree of hydrogenation of the hydrogenated nitrile rubber and its modified compounds is ≥99%; and / or; The weight average molecular weight of the polyvinylidene fluoride and its modified compounds is 2 million to 4 million; and / or; The crystallinity of the polyvinylidene fluoride and its modified compounds is 40% to 60%.
14. The battery cell according to any one of claims 1 to 13, characterized in that: The membrane resistance of the positive electrode plate is less than or equal to 1Ω.
15. The battery cell according to any one of claims 1 to 14, characterized in that: The film resistance of the positive electrode plate is 0.1Ω~1Ω.
16. The battery cell according to any one of claims 1 to 15, characterized in that: The particle size of the first positive electrode active material and / or the second positive electrode active material satisfies: Dv50 is 0.5 μm to 1.5 μm; and / or; A carbon coating layer is formed on the outer side of the particles of the first positive electrode active material and / or the second positive electrode active material, and the thickness of the carbon coating layer is 0.01 μm to 1 μm.
17. The secondary battery according to any one of claims 1 to 16, characterized in that: A distance H between the first surface and the second surface is 0.1 mm to 0.2 mm.
18. A battery device, characterized in that: A secondary battery comprising the secondary battery according to any one of claims 1 to 17.
19. An electrical device, characterized in that: A battery device comprising the battery device of claim 18.
Citation Information
Patent Citations
Battery
CN111200108A
Positive pole piece, lithium ion secondary battery, battery module, battery pack and electric device
CN115842114A
Positive plate as well as preparation method and application thereof
CN117174838A
Positive pole piece and lithium ion battery
CN117374224A
Cited By
Battery cell, battery device, electric device, and energy storage device
CN120300267A
Battery cell, battery device, power consuming device, and energy storage device
CN120300267B
Battery cell, battery device, electric device, and energy storage device
CN120300268A
Battery cells, battery packs, electrical devices, and energy storage devices
CN120300268B
Battery cell, manufacturing method therefor, battery apparatus and electrical apparatus
WO2026157408A1